Barrier film, multilayer object, wavelength conversion sheet, backlight member, and display device

The barrier film with a structured lamination of aluminum oxide vapor deposition films and hydroxyl-containing coating layers addresses the brightness maintenance issue in wavelength conversion sheets by significantly improving the oxygen and water vapor barrier properties, thereby extending the luminance maintenance rate.

JP2025060397APending Publication Date: 2025-04-10DAI NIPPON PRINTING CO LTD

Patent Information

Application Number
JP2024106164
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-29
Filing Date
2024-07-01
Publication Date
2025-04-10

AI Technical Summary

Technical Problem

Existing wavelength conversion sheets face challenges in maintaining brightness over time due to deterioration of the phosphor layer, which requires improved oxygen and water vapor barrier properties in the barrier film.

Method used

A barrier film is developed with a specific structure comprising a resin substrate, alternating layers of aluminum oxide vapor deposition films and coating layers, where the coating layers are made of a resin composition containing alkoxysilane and water-soluble resins with hydroxyl groups. The film's barrier properties are enhanced by controlling the peak top ratio of the aluminum oxide vapor deposition films through X-ray absorption fine structure analysis.

Benefits of technology

The improved barrier film effectively maintains luminance over a longer period, enhancing the brightness maintenance rate of the wavelength conversion sheet and ensuring stable performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025060397000007
    Figure 2025060397000007
  • Figure 2025060397000008
    Figure 2025060397000008
  • Figure 2025060397000009
    Figure 2025060397000009
Patent Text Reader

Abstract

To provide: a barrier film which, when used in a wavelength conversion sheet, can attain a high retention of luminance; and a wavelength conversion sheet and a backlight member that employ the barrier film.SOLUTION: The barrier film comprises a resin substrate, a first vapor-deposited aluminum oxide film, a first coating layer, a second vapor-deposited aluminum oxide film and a second coating layer, which are laminated in this order. The first and second coating layers are each a cured product of a resin composition containing alkoxysilane and a hydroxyl-group-containing water-soluble resin. The first and second vapor-deposited aluminum oxide films exhibit a vapor-deposited-film peak top ratio P greater than or equal to 0.70 and less than 1.05 when X-ray absorption fine structure analysis is performed, where P=(intensity peak top around 1572 eV) / (intensity peak top around 1566 eV).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a barrier film, a laminate, a wavelength conversion sheet, a backlight member, and a display device. [Background technology]

[0002] Conventionally, laminated films having a film formed on a substrate such as a long film or sheet of plastic etc. have been used for various purposes. For example, a barrier laminated film has been developed in which a barrier layer made of a thin film of aluminum oxide etc. is provided on a plastic film to provide a barrier function against oxygen and water vapor.

[0003] For example, Patent Document 1 discloses a gas barrier film having excellent transparency and gas barrier properties, which is obtained by using a plasma activated deposition method (a so-called plasma assisted deposition method) that generates high-density plasma in the space between an aluminum evaporation source and a polymer film, as a method for producing a barrier film having an aluminum oxide thin film.

[0004] Furthermore, Patent Document 2 discloses an aluminum oxide vapor-deposited film in which a vapor-deposited film of low aluminum oxide is formed on a transparent plastic film, which is then subjected to a plasma treatment containing oxygen gas to form a vapor-deposited film of high aluminum oxide, which is then further subjected to a heat treatment at high humidity to form a vapor-deposited film of aluminum hydroxide.

[0005] Meanwhile, development of backlight components using quantum dot technology is also underway as an application of the above-mentioned barrier film. Quantum dots are nanometer-sized semiconductor particles. In addition, quantum dots can adjust the emission wavelength over the entire visible range by adjusting the size due to the quantum confinement effect (quantum size effect) in which electrons and excitons are confined in small nanometer-sized crystals. Quantum dots are phosphors that can generate strong fluorescence in a narrow wavelength band, so that a display device can be illuminated with three primary colors of light with excellent color purity. Therefore, a backlight using quantum dots can be used to create a display device with excellent color reproducibility.

[0006] The wavelength conversion sheet used in the backlight light source of this display device has a phosphor layer in which nanometer-sized semiconductor particles are dispersed in a resin layer, and barrier films are laminated on both surfaces of the phosphor layer to prevent deterioration of the phosphor layer, and is combined with an LED light source.

[0007] For example, a wavelength conversion sheet in which a barrier film is laminated on a phosphor layer containing a phosphor, the barrier film being a wavelength conversion sheet in which a barrier layer is laminated on one side of a specified polyethylene terephthalate film, and a backlight unit using the same have been developed (Patent Document 3). By using a wavelength conversion sheet using a barrier film with excellent barrier properties and transparency, a display device with more natural, vivid colors and excellent color tones can be provided. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2017-177343 A [Patent Document 2] Japanese Patent Application Publication No. 11-170427 [Patent Document 3] WO2015 / 037733 Summary of the Invention [Problem to be solved by the invention]

[0009] In the wavelength conversion sheet as disclosed in Patent Document 3, further improvement in the oxygen barrier property and water vapor barrier property of the barrier film is required to suppress deterioration of the phosphor layer. In particular, the luminance of the wavelength conversion sheet decreases over time due to deterioration of the phosphor layer. Therefore, in order to maintain the luminance of the wavelength conversion sheet for a long period of time, a particularly high level of barrier property is required.

[0010] An object of the present invention is to provide a barrier film that is suitably used for an optical film such as a wavelength conversion sheet, a wavelength conversion sheet using the barrier film, and a backlight member using the wavelength conversion sheet. [Means for solving the problem]

[0011] As a result of intensive studies to solve the above problems, the present inventors have found that by focusing on the amount of hydroxyl groups in an aluminum oxide thin film obtained by X-ray absorption fine structure analysis (hereinafter simply referred to as XAFS), the luminance maintenance rate can be increased when a barrier film is used as a wavelength conversion sheet, and have completed the present invention.

[0012] Specifically, the present invention provides the following:

[0013] (1) A barrier film comprising a resin substrate, a first aluminum oxide vapor-deposited film, a first coating layer, a second aluminum oxide vapor-deposited film, and a second coating layer laminated in this order, Each of the first coating layer and the second coating layer is a cured product of a resin composition containing an alkoxysilane and a hydroxyl group-containing water-soluble resin, a vapor-deposited film peak top ratio P defined as follows, of 0.70 or more and less than 1.05, when the first aluminum oxide vapor-deposited film and the second aluminum oxide vapor-deposited film are subjected to X-ray absorption fine structure analysis from the second coating layer surface side of the barrier film. P = (peak intensity at around 1572 eV) / (peak intensity at around 1566 eV)

[0014] (2) The barrier film according to (1), wherein when the barrier film is etched from a surface side opposite to the resin substrate by time-of-flight secondary ion mass spectrometry (TOF-SIMS), a coating layer intensity ratio X, defined as follows, detected in each region of the first coating layer and the second coating layer is 0.50 or more and 1.10 or less, respectively. X=C2 - Ionic strength / Si - Ionic Strength

[0015] (3) The barrier film according to (1), further comprising a matte layer disposed on the resin substrate opposite to the first aluminum oxide vapor-deposited film.

[0016] (4) A laminate comprising the barrier film according to (1) and a support laminated via an adhesive layer.

[0017] (5) The laminate according to (4), further comprising a matte layer disposed on the side of the support opposite to the adhesive layer.

[0018] (6) A wavelength conversion sheet in which the barrier films according to (3) are disposed on both sides of a phosphor layer, sandwiching the phosphor layer therebetween.

[0019] (7) A wavelength conversion sheet in which the laminate according to (4) is disposed on both sides of a phosphor layer, and each of the laminates is disposed in the order of the support, the resin base material, the covering layer, and the phosphor layer from the outermost layer side.

[0020] (8) A wavelength conversion sheet in which the laminate according to (4) is disposed on both sides of a phosphor layer, and each of the laminates is disposed in the order of the support, the covering layer, the resin base material, and the phosphor layer from the outermost layer side.

[0021] (9) A wavelength conversion sheet in which the laminates according to (4) are arranged on both sides of a phosphor layer, one laminate being arranged in the order of the support, the resin base material, the covering layer, and the phosphor layer from the outermost layer side, and the other laminate being arranged in the order of the support, the covering layer, the resin base material, and the phosphor layer from the outermost layer side.

[0022] (10) A backlight member comprising a light source, a light guide plate or a diffusion plate, and the wavelength conversion sheet according to (6).

[0023] (11) A surface-mount display device having a light guide plate, A liquid crystal panel, a polarized light selective reflection sheet, a prism sheet, the wavelength conversion sheet according to (6), the light guide plate, and a reflection sheet are laminated in this order, A light source unit is disposed on an end surface of the light guide plate. Display device.

[0024] (12) A direct-type display device having a diffusion plate, A liquid crystal panel, a polarized light selective reflection sheet, a prism sheet, the wavelength conversion sheet according to (6), the diffusion plate, a light source unit, and a reflection sheet are laminated in this order. Display device. Effect of the Invention

[0025] The barrier film of the present invention can increase the luminance maintenance rate when used in a wavelength conversion sheet. [Brief description of the drawings]

[0026] [Figure 1] FIG. 1 is a cross-sectional view showing an example of a barrier film according to an embodiment of the present invention. [Diagram 2] 1 is a diagram showing an example of a film forming apparatus according to an embodiment of the present invention; [Diagram 3] FIG. 2 is a cross-sectional view showing an example of a plasma pretreatment mechanism of a film forming apparatus. [Figure 4] 2 is a plan view showing an example of an electrode unit and a magnetic field generating unit of a plasma pretreatment mechanism of a film forming apparatus. FIG. [Diagram 5] 2 is a cross-sectional view showing an example of an electrode unit and a magnetic field generating unit of a plasma pretreatment mechanism of a film forming apparatus. FIG. [Figure 6] FIG. 2 is a cross-sectional view showing an example of a film formation mechanism of a film formation apparatus. [Figure 7] FIG. 1 is a cross-sectional view showing an example of a laminate using the barrier film of the present invention. [Figure 8] FIG. 2 is a cross-sectional view showing another example of a laminate using the barrier film of the present invention. [Figure 9] FIG. 2 is a cross-sectional view showing another example of a laminate using the barrier film of the present invention. [Figure 10] FIG. 1 is a cross-sectional view showing an example of a wavelength conversion sheet using the barrier film of the present invention. [Figure 11] FIG. 11 is a cross-sectional view showing another example of a wavelength conversion sheet using the barrier film of the present invention. [Figure 12] 1 is a perspective view showing a schematic configuration of a surface-mounted display device according to an embodiment of the present invention; [Figure 13] FIG. 11 is a cross-sectional view of the display device shown in FIG. [Figure 14] 1 is a cross-sectional view illustrating a schematic configuration of a direct-type display device according to an embodiment of the present invention. [Figure 15] FIG. 1 shows an XAFS spectrum of the barrier film of Example 3. [Figure 16] FIG. 13 is a diagram showing the results of XAFS spectrum analysis of the barrier film of Example 3. [Figure 17] FIG. 13 is a diagram showing the results of XAFS spectrum analysis of the barrier film of Comparative Example 2. [Figure 18] FIG. 13 is a diagram showing the results of XAFS spectrum analysis of the barrier film of Comparative Example 4. [Figure 19] FIG. 13 is a diagram showing the results of XAFS spectrum analysis of the barrier film of Comparative Example 10. [Figure 20] FIG. 13 shows the results of a TOF-SIMS spectrum for the barrier film of Example 3. [Figure 21]FIG. 13 is a diagram showing the results of a TOF-SIMS spectrum for the barrier film of Comparative Example 10. [Figure 22] FIG. 13 is a diagram showing the results of a TOF-SIMS spectrum for the barrier film of Comparative Example 11. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0027] Specific embodiments of the present invention will be described in detail below, but the present invention is not limited to the following embodiments and can be modified as appropriate within the scope of the object of the present invention. In addition, in this specification, the expression "A to B" (A and B are arbitrary numbers) means "AX or more and B or less."

[0028] FIG. 1 is a cross-sectional view showing an example of a barrier film according to the present embodiment. A barrier film manufactured using the film forming apparatus according to the present embodiment includes, for example, a substrate 120, a first vapor-deposited film 131b, a first coating layer 131a, a second vapor-deposited film 132b, and a second coating layer 132a, as in the barrier film 100A shown in FIG. 1. In the example shown in FIG. 1, the first vapor-deposited film 131b is located on one surface of the substrate 120. In the example shown in FIG. 1, the barrier film 100A is laminated in the order of the substrate 120, the first vapor-deposited film 131b, the first coating layer 131a, the second vapor-deposited film 132b, and the second coating layer 132a, and the second coating layer 132a is located on the surface of the barrier film. First deposited film 131b, first covering layer 131a, second deposited film 132b and second covering layer 132a constitute barrier layer 130. In the present invention, the first aluminum oxide deposited film will be simply referred to as the first deposited film, and the second aluminum oxide deposited film will be simply referred to as the second deposited film in the following description.

[0029] In this specification, "laminated in this order" means that the substrate, the first vapor-deposited film, the first coating layer, the second vapor-deposited film, and the second coating layer are laminated in this order, and other layers, such as an anchor coat layer or a primer layer, may be laminated between these layers.

[0030] Each layer constituting the barrier film 100A will be described below.

[0031] [Base material] The substrate 120 is a layer made of a resin. The resin is not particularly limited, and a known resin film or sheet can be used. Specifically, the substrate may be a polyester substrate or a polyolefin substrate. As the polyester substrate, for example, a polyester resin including a polyethylene terephthalate resin, a polybutylene terephthalate resin, a polyethylene naphthalate resin, or the like can be used. As the polyolefin substrate, for example, a polypropylene resin can be used.

[0032] Among polyester-based resins, it is preferable to use polyethylene terephthalate-based resins and polybutylene terephthalate-based resins. The polyester film used as the substrate 120 may be stretched in a predetermined direction. In this case, the polyester film may be a uniaxially stretched film stretched in one predetermined direction, or a biaxially stretched film stretched in two predetermined directions. For example, when a film made of polyethylene terephthalate is used as the substrate 120, a biaxially stretched polyethylene terephthalate film can be used.

[0033] When a film made of polypropylene resin is used as the base material 120, a biaxially oriented polypropylene film can be used.

[0034] In the case of polyester films, the thickness is not particularly limited as long as it allows pretreatment and film formation treatment when forming a vapor-deposited film using a film-forming device described later, but from the viewpoint of flexibility and shape retention, the thickness is preferably in the range of 5 μm to 100 μm, and more preferably in the range of 10 μm to 50 μm. If the thickness of the polyester film is within the above range, it is easy to bend and does not break during transportation, and is easy to handle in a film-forming device used for producing a barrier film having a vapor-deposited film.

[0035] As the polyethylene terephthalate film (PET film), in addition to conventionally known PET films, biomass PET film, recycled PET film, and high stiffness PET film (tough PET film) may be used as the substrate. It may have a single layer or a multi-layer structure of two or more layers, and in the case of a multi-layer structure, the layers may have the same composition or different compositions. In the case of a multi-layer structure, each layer may be bonded with an adhesive layer or the like.

[0036] In the case of a polyolefin film, the film thickness is preferably in the range of 10 μm or more and 100 μm or less, more preferably in the range of 15 μm or more and 50 μm or less, from the viewpoints of flexibility and shape retention.

[0037] The substrate 120 may have an anchor coat layer (AC layer, also called a primer layer) formed on its surface to enhance adhesion with the deposition film. Examples of the anchor coat layer include polyurethane resin, polyamide resin, epoxy resin, phenol resin, (meth)acrylic resin, and polyvinyl acetate resin. Examples of the polyurethane resin include acrylic urethane resin and polyester urethane resin.

[0038] The substrate 120 of the roll is preferably moisture-conditioned in advance in a manufacturing process or moisture-conditioning process. This can improve the barrier properties. It can also prevent the substrate from breaking during plasma-assisted deposition, which will be described later. One example of moisture-conditioning conditions is storing the substrate at a temperature of 22 to 30° C. and a relative humidity of 40 to 65% RH for 1 to 7 days. Rewinding the roll before storage is also effective for moisture conditioning. In this case, the rewinding process is preferably performed under the above moisture-conditioning conditions.

[0039] [Vapor deposition film] Next, the first vapor-deposited film 131b and the second vapor-deposited film 132b (hereinafter, both are simply referred to as vapor-deposited films without distinction between them) will be described. The vapor-deposited film contains aluminum oxide. In the vapor-deposited film, at least a part of aluminum exists in the form of Al2O3. The vapor-deposited film may further contain metal oxides such as silicon oxide, silicon nitride, silicon oxynitride, silicon carbide, magnesium oxide, titanium oxide, tin oxide, indium oxide, zinc oxide, and zirconium oxide, or metal nitrides and carbides thereof. The first vapor-deposited film 131b and the second vapor-deposited film 132b may be the same or different.

[0040] The lower limit of the thickness of the deposited film is preferably 3 nm or more, more preferably 5 nm or more. The upper limit is preferably 100 nm or less, more preferably 50 nm or less, particularly preferably 15 nm or less. The first deposited film 131b and the second deposited film 132b may be the same or different.

[0041] In the present invention, the term "aluminum oxide vapor deposition film" means, as described above, "a vapor deposition film containing aluminum oxide", and may contain aluminum oxide hydroxide AlO(OH) and aluminum hydroxide Al(OH)3 in addition to aluminum oxide Al2O3. This will be explained in detail below.

[0042] (XAFS Spectral Analysis) XAFS analysis is an X-ray absorption fine structure (XAFS) spectrum, in which X-rays are irradiated from the surface side of the vapor deposition surface of the barrier film (the coating layer side if there is a coating layer) and the amount of absorption is measured. Detailed measurement and analysis conditions are described in the examples.

[0043] In particular, XAFS spectrum analysis of soft X-rays using synchrotron radiation can provide bulk information on the entire deposited film, not just a portion of the surface side of the deposited film, and can provide information on the size of hydroxyl groups in the aluminum oxide deposited film. Even if a coating layer or the like is present on the surface of the deposited film, information on the deposited film in the presence of the coating layer can be obtained by irradiating the deposited film from the surface side of the coating layer through the coating layer. Note that, when the first deposited film 131b and the second deposited film 132b are provided as in the configuration of Figure 1, a bulk XAFS spectrum can be obtained for the combined state of the two deposited films.

[0044] Fig. 15 shows an example of the results of XAFS measurement of an example of a barrier film in an example described later. Fig. 16 shows each peak obtained by peak separation of the XAFS spectrum in Example 3. In Figs. 15 and 16, the vertical axis is absorption intensity (au) and the horizontal axis is energy (eV). The evaporated film peak top ratio P in the present invention is the ratio obtained from each peak top after peak separation of the XAFS spectrum, as shown in Fig. 16, for example.

[0045] In the peak separation analysis in Figure 16, Experiment is the measured XAFS spectrum, Fit.Peak1 is the separated 1566 eV intensity peak, Fit.Peak2 is the separated 1568 eV intensity peak, and Fit.Peak3 is the separated 1572 eV intensity peak. Fit.Base1 is the baseline at 1566 eV, and Fit.Base2 is the baseline at 1568 eV.

[0046] 15 and 16, the XAFS spectrum has multiple peaks, specifically, peak P1 with a top near 1566 eV, peak P2 with a top near 1568 eV, and peak P3 with a top near 1572 eV. Note that "near 1566 eV" refers to 1565 eV or more and 1567 eV or less, "near 1568 eV" refers to more than 1567 eV and 1569 eV or less, and "near 1572 eV" refers to 1571 eV or more and 1573 eV or less.

[0047] Here, P1 is considered to be a peak derived from 4-coordinate aluminum oxide, P2 from 6-coordinate aluminum oxide, and P3 from 6-coordinate aluminum hydroxide and aluminum oxide hydroxide.

[0048] It is believed that an amorphous aluminum oxide film has better flexibility than a crystalline film, so it is preferable for it to be amorphous when used as a barrier film. However, it has been difficult to confirm whether a film is crystalline or amorphous using XRD, a conventional X-ray analysis, except when a clear crystalline peak can be confirmed.

[0049] When checking the XAFS spectrum, γ-Al2O3 and θ-Al2O3 are examples of crystalline aluminum oxide films in which P1 is detected, but the P1 peak is never relatively higher than the P2 peak. According to the examples of the present application described later, for example, in Example 3 (see FIG. 16), it is clear that P1>P2, and it can be confirmed that an amorphous film has been formed.

[0050] Furthermore, it is considered that the condition of the aluminum oxide film to withstand the brightness maintenance rate test (described in the examples below) when used in a wavelength conversion sheet is not sufficient to be amorphous, and the introduction of hydroxyl groups is necessary. However, for example, in the depth analysis using conventional TOF-SIMS, it is unclear whether the aluminum oxide film is evaluated or the moisture remaining at the interface between the aluminum oxide film and the substrate is detected, and sufficient depth resolution cannot be obtained in the aluminum oxide film when a coating layer is present, and the like, and therefore the correlation between the film formation conditions and the film quality could not be fully investigated.

[0051] According to the present invention, by checking the XAFS spectrum and defining the peak top ratio of the evaporated film as P=P3 peak top / P1 peak top=(intensity peak top at about 1572 eV) / (intensity peak top at about 1566 eV), information regarding the amount of hydroxyl groups in the evaporated aluminum oxide film can be obtained.

[0052] The present invention has found that the gas barrier property changes depending on the value of the vapor-deposited film peak top ratio P. Specifically, by making the vapor-deposited film peak top ratio P 0.70 or more and less than 1.05, the luminance maintenance rate can be improved when used in a wavelength conversion sheet. The lower limit of the vapor-deposited film peak top ratio P is preferably 0.75 or more, more preferably 0.80 or more, and particularly preferably 0.81 or more. The upper limit of the vapor-deposited film peak top ratio P is preferably 1.00 or less, more preferably 0.90 or less, and particularly preferably 0.93 or less.

[0053] If the peak top ratio P of the evaporated film is less than 0.70, the amount of hydroxyl groups introduced is too small, resulting in poor film flexibility and reduced gas barrier properties.If the peak top ratio P of the evaporated film is 1.05 or more after high-temperature and high-humidity moist heat treatment, the amount of hydroxyl groups introduced is too large, resulting in reduced initial barrier properties, particularly water vapor barrier properties.

[0054] In the present invention, the luminance maintenance rate in the examples described later can be 95% or more. Although the luminance maintenance rate is qualitatively correlated with the barrier property, the test conditions for the luminance maintenance rate are severe conditions in which the film is placed in a thermo-hygrostat chamber at 60°C and 90% RH and left to stand for 1000 hours, and therefore, even if there is no difference in the oxygen and water vapor barrier properties near the measurement limit, there will be a difference in the luminance maintenance rate.

[0055] The peak top ratio P of the vapor-deposited film in the barrier film can be adjusted by controlling the combination of the plasma pretreatment, the plasma assisted treatment during vapor deposition, the aging treatment after the film-forming process, and the aging treatment after the coating layer forming process. In particular, the luminance maintenance rate can be improved when used in a wavelength conversion sheet by using a combination in which the oxidation of aluminum is promoted by the plasma assisted treatment during vapor deposition, and then the introduction of hydroxyl groups is promoted by the aging treatment after the film-forming process. These results are supported by the examples described later.

[0056] (covering layer) The first coating layer 131a laminated on the surface of the first aluminum oxide vapor deposition film 131b and the second coating layer 132a laminated on the surface of the second aluminum oxide vapor deposition film 132b mechanically and chemically protect the aluminum oxide vapor deposition film and improve the barrier performance of the laminated film having barrier properties. Hereinafter, the first coating layer 131a and the second coating layer 132a (hereinafter, both are simply referred to as coating layers without distinction) coated to form a barrier laminated film will be described. In the following description, the first coating layer 131a and the second coating layer 132a may be the same or different in material, composition, film thickness, etc.

[0057] The coating layer is formed by applying a barrier coating agent onto the aluminum oxide vapor deposition film and solidifying it. The barrier coating agent is composed of a metal alkoxide, a water-soluble polymer, a silane coupling agent (if necessary), a sol-gel catalyst, an acid, etc.

[0058] As the metal alkoxide, the general formula R1 n M(OR 2 ) m (wherein, in the formula, R1 and R2 represent an organic group having 1 to 8 carbon atoms, M represents a metal atom, n represents an integer of 0 or more, m represents an integer of 1 or more, and n+m represents the atomic valence of M), and examples of the metal atom represented by M of the metal alkoxide include silicon, zirconium, titanium, aluminum, and the like. For example, it is preferable to use an alkoxysilane in which M is Si.

[0059] The above alkoxysilane is, for example, one represented by the general formula Si(ORa)4 (wherein Ra represents a lower alkyl group). In the above, Ra may be a methyl group, an ethyl group, an n-propyl group, an n-butyl group, or the like. Specific examples of the above alkoxysilane include tetramethoxysilane Si(OCH3)4, tetraethoxysilane Si(OC2H5)4, tetrapropoxysilane Si(OC3H7)4, tetrabutoxysilane Si(OC4H9)4, and the like. The above alkoxides may be used in combination of two or more kinds.

[0060] Silane coupling agents having reactive groups such as vinyl, epoxy, methacryl, and amino groups can be used. In particular, organoalkoxysilanes having epoxy groups are suitable, and for example, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropylmethyldimethoxysilane, γ-glycidoxypropyldimethylmethoxysilane, γ-glycidoxypropyltriethoxysilane, γ-glycidoxypropylmethyldiethoxysilane, γ-glycidoxypropyldimethylethoxysilane, or β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane can be used. The above-mentioned silane coupling agents may be used alone or in combination of two or more.

[0061] In particular, the crosslink density of the cured film of the coating layer using bifunctional compounds such as γ-glycidoxypropylmethyldimethoxysilane and γ-glycidoxypropylmethyldiethoxysilane is lower than that of a system using trialkoxysilane. Therefore, the cured film has excellent gas barrier properties and hot water treatment resistance, and is flexible, and has excellent bending resistance, so that the gas barrier properties of the barrier film are not easily deteriorated.

[0062] The water-soluble polymer may be a polyvinyl alcohol resin or an ethylene-vinyl alcohol copolymer, or may be a combination of a polyvinyl alcohol resin and an ethylene-vinyl alcohol copolymer. In the coating layer according to the present embodiment, a polyvinyl alcohol resin is preferred.

[0063] Generally, the polyvinyl alcohol resin can be one obtained by saponifying polyvinyl acetate. The polyvinyl alcohol resin can be a partially saponified polyvinyl alcohol resin in which several tens of percent of acetate groups remain, a completely saponified polyvinyl alcohol in which no acetate groups remain, or a modified polyvinyl alcohol resin in which OH groups have been modified. As the polyvinyl alcohol resin, it is necessary to use at least one that undergoes crystallization to improve the film hardness of the gas barrier coating film, and preferably has a saponification degree of 70% or more. In addition, any polyvinyl alcohol resin can be used as long as it has a polymerization degree within the range used in the conventional sol-gel method (about 100 to 5000). Examples of such polyvinyl alcohol resins include RS resin "RS-110 (saponification degree = 99%, polymerization degree = 1,000)" manufactured by Kuraray Co., Ltd. and "GOHSENOL NM-14 (saponification degree = 99%, polymerization degree = 1,400)" manufactured by Nippon Synthetic Chemical Industry Co., Ltd.

[0064] The ethylene-vinyl alcohol copolymer may be a saponified copolymer of ethylene and vinyl acetate, i.e., a product obtained by saponifying an ethylene-vinyl acetate random copolymer. For example, it may be a partially saponified product in which several tens of mol% of acetate groups remain, or a completely saponified product in which only a few mol% of acetate groups remain or no acetate groups remain, and is not particularly limited. However, from the viewpoint of barrier properties, the lower limit of the saponification degree is preferably 80% or more, more preferably 90% or more, and even more preferably 95% or more. The upper limit is 100% or less.

[0065] As the sol-gel catalyst, an acid or amine compound is preferable.

[0066] As the acid, for example, mineral acids such as sulfuric acid, hydrochloric acid, nitric acid, etc., and organic acids such as acetic acid, tartaric acid, etc. can be used.

[0067] The content of the acid is preferably 0.001 to 0.05 mol%, more preferably 0.01 to 0.03 mol%, based on the total molar amount of alkoxy groups in the metal alkoxide. If the content is less than 0.001%, the catalytic effect is too small, whereas if the content is more than 0.05 mol%, the catalytic effect is too strong, causing the reaction rate to become too fast and tending to become non-uniform.

[0068] As the amine compound, a tertiary amine that is substantially insoluble in water and soluble in an organic solvent is preferable. Specifically, for example, N,N-dimethylbenzylamine, tripropylamine, tributylamine, tripentylamine, etc. can be used. In particular, N,N-dimethylbenzylamine is preferable.

[0069] The content of the amine compound is preferably, for example, 0.01 to 1.0 part by mass, particularly 0.03 to 0.3 part by mass, per 100 parts by mass of the metal alkoxide. If the content is less than 0.01 part by mass, the catalytic effect is too small, whereas if the content is more than 1.0 part by mass, the catalytic effect is too strong, causing the reaction rate to become too fast and tending to become non-uniform.

[0070] As the solvent, it is preferable to use water or alcohol such as methyl alcohol, ethyl alcohol, n-propyl alcohol, isopropanol, or n-butanol.

[0071] The barrier coating layer formed as described above has a layer thickness of 100 to 500 nm. This range is preferable because the coating film does not crack and sufficiently covers the surface of the deposited film.

[0072] The composition of the barrier coating agent can be 100 parts by mass of alkoxysilane, 5 to 10 parts by mass of water-soluble polymer such as polyvinyl alcohol resin, and 1 to 10 parts by mass of silane coupling agent. This allows the flexibility of the film to be maintained. In the above, if the silane coupling agent is used in an amount exceeding 20 parts by mass, the rigidity and brittleness of the barrier coating film formed increases, which is not preferable.

[0073] Furthermore, when a silane coupling agent is not contained, the ratio of metal alkoxide can be reduced and the barrier properties can be improved by using 10 to 20 parts by mass of a water-soluble polymer such as a polyvinyl alcohol resin per 100 parts by mass of alkoxysilane.

[0074] The lower limit of the IO value (the solid content ratio of metal alkoxide such as tetraethoxysilane (SiO2 equivalent) to water-soluble resin such as polyvinyl alcohol) in the coating layer is preferably 1.5 or more, more preferably 1.9 or more. The upper limit is preferably 4.5 or less, more preferably 3.5 or less. If it exceeds 4.5, the coating layer loses flexibility and cracks easily occur, which reduces the barrier properties, which is undesirable. If it is less than 1.5, the condensation of the hydrolyzate generated from the metal alkoxide does not proceed sufficiently, which reduces the moist heat resistance, which is undesirable.

[0075] (C2 / Si ratio analysis by TOF-SIMS) When the coating layer is etched from the surface side of the barrier film opposite the resin substrate by time-of-flight secondary ion mass spectrometry (TOF-SIMS), the coating layer intensity ratio X, defined as below, detected in each region of the first coating layer and the second coating layer is 0.50 or more and 1.10 or less. X=C2 - Ionic strength / Si - Ionic Strength

[0076] The coating layer intensity ratio X of the coating layer of the barrier film according to the present embodiment will be described with reference to Example 3 (FIG. 20) described later. FIG. 20 is an example of a graph analysis diagram showing the detection intensity of secondary ions reflecting element species and chemical structure information when the barrier film of Example 3, which has the layer structure of FIG. 1, is etched (analyzed in the depth direction) from the surface side (surface side opposite to the substrate) of the second coating layer 132a using time-of-flight secondary ion mass spectrometry (TOF-SIMS) to measure element species and chemical structure information contained in the barrier film. The unit of the vertical axis of the graph is the intensity of the detected secondary ions, which is expressed by taking a common logarithm. The unit of the horizontal axis of the graph (Et times) is the etching time (seconds).

[0077] TOF-SIMS (Time-of-Flight Secondary Ion Mass Spectrometry) is a method in which a pulsed primary ion beam is irradiated onto the surface of a solid sample to be analyzed, and the secondary ions sputtered and released from the sample surface are mass-separated and analyzed using their flight time difference (flight time is proportional to the square root of mass).

[0078] Specifically, when performing analysis in the depth direction, the second coating layer 132a and the first coating layer 131a are measured using a time-of-flight secondary ion mass spectrometer while soft etching is repeated at a constant speed from the outermost surface of the second coating layer 132a using a Cs (cesium) ion gun, thereby obtaining graphs of the detection intensities of secondary ions that reflect element species and chemical structure information. As a specific example, as shown in FIG. 20, the ion intensity is shown as C2 - Ion, CN - Ion, Si - Ion, AlO2 - Ion, SiO2 - 1 is a graph showing the intensity of ions detected from the surface side according to the etching time. - Ionic strength and Si - Ion intensity and AlO2 derived from the second vapor deposition film 132b -Ion strength and C2 derived from the first coating layer 131a - Ionic strength and Si - Ion intensity and AlO2 derived from the first vapor deposition film 131b - Ionic strength and PET-derived C2 - The ionic intensity is then observed.

[0079] In the barrier film of the present invention, the coating layer intensity ratios X, defined as below, detected in the respective regions of the first coating layer 131a and the second coating layer 132a are each 0.50 or more and 1.10 or less. X=C2 - Ionic strength / Si - Ionic Strength Here, the coating layer intensity ratio X is an average value of each coating layer region, and in Fig. 20, the calculation is performed by setting the region of the second coating layer 132a at 500 to 2500 seconds and the region of the first coating layer 131a at 4500 to 6500 seconds, as an example. The details of the TOF-SIMS measurement conditions are the conditions described in the Examples.

[0080] If the coating layer strength ratio X is less than 0.50, the coating layer loses flexibility and becomes more susceptible to cracking, which reduces the barrier properties, and if it exceeds 1.10, the low Si concentration reduces the moist heat resistance, which is also undesirable.

[0081] (Film forming equipment) Next, an example of a film forming apparatus 10 used in the manufacturing method of a barrier film will be described. As shown in Fig. 2, the film forming apparatus 10 includes a substrate transport mechanism 11A for transporting a substrate 1 (corresponding to the substrate 120 described above), a plasma pretreatment mechanism 11B for performing plasma pretreatment on the surface of the substrate 1, and a film forming mechanism 11C for forming a vapor deposition film. In the example shown in Fig. 5, the film forming apparatus 10 further includes a decompression chamber 12. The decompression chamber 12 has a decompression mechanism, such as a vacuum pump described later, for adjusting the atmosphere in at least a part of the space inside the decompression chamber 12 to atmospheric pressure or lower.

[0082] In the example shown in Fig. 2, the decompression chamber 12 includes a substrate transport chamber 12A in which the substrate transport mechanism 11A is located, a plasma pretreatment chamber 12B in which the plasma pretreatment mechanism 11B is located, and a film formation chamber 12C in which the film formation mechanism 11C is located. The decompression chamber 12 is preferably configured to suppress the atmospheres inside the respective chambers from mixing with each other. For example, as shown in Fig. 2, the decompression chamber 12 may be located between the substrate transport chamber 12A and the plasma pretreatment chamber 12B, between the plasma pretreatment chamber 12B and the film formation chamber 12C, and between the substrate transport chamber 12A and the film formation chamber 12C, and may have partition walls 35a to 35c that separate the respective chambers.

[0083] The substrate transfer chamber 12A, the plasma pretreatment chamber 12B, and the film formation chamber 12C will be described. The plasma pretreatment chamber 12B and the film formation chamber 12C are each provided in contact with the substrate transfer chamber 12A, and each has a portion connected to the substrate transfer chamber 12A. This allows the substrate to be transferred between the substrate transfer chamber 12A and the plasma pretreatment chamber 12B, and between the substrate transfer chamber 12A and the film formation chamber 12C without being exposed to the atmosphere. For example, between the substrate transfer chamber 12A and the plasma pretreatment chamber 12B, the substrate 1 can be transferred through an opening provided in the partition wall 35a. The substrate transfer chamber 12A and the film formation chamber 12C have the same structure, and the substrate can be transferred between the substrate transfer chamber 12A and the film formation chamber 12C.

[0084] The function of the decompression mechanism of the decompression chamber 12 will be described. The decompression mechanism of the decompression chamber 12 is configured to reduce the pressure of the atmosphere in the space in which at least the plasma pretreatment mechanism 11B or the film formation mechanism 11C of the film formation apparatus 10 is disposed to below atmospheric pressure. The decompression mechanism may be configured to reduce the pressure of each of the substrate transfer chamber 12A, the plasma pretreatment chamber 12B, and the film formation chamber 12C, which are partitioned by partition walls 35a to 35c, to below atmospheric pressure.

[0085] The configuration of the decompression mechanism of the decompression chamber 12 will be described. The decompression chamber 12 may have, for example, a vacuum pump connected to the plasma pretreatment chamber 12B. By adjusting the vacuum pump, the pressure in the plasma pretreatment chamber 12B when performing the plasma pretreatment described later can be appropriately controlled. In addition, the plasma supplied into the plasma pretreatment chamber 12B can be prevented from diffusing to other chambers by a method described later. The decompression mechanism of the decompression chamber 12 may have a vacuum pump connected to the film formation chamber 12C, similar to the vacuum pump connected to the plasma pretreatment chamber 12B. As the vacuum pump, a dry pump, a turbo molecular pump, a cryopump, a rotary pump, a diffusion pump, or the like can be used.

[0086] A substrate transport mechanism 11A for the substrate 1 of the film forming apparatus 10 according to the present embodiment will be described together with a transport path of the substrate 1. The substrate transport mechanism 11A is a mechanism arranged in the substrate transport chamber 12A for transporting the substrate 1. In the example shown in FIG. 2, the substrate transport mechanism 11A has an unwinding roller 13 to which a roll-shaped original web of the substrate 1 is attached, a winding roller 15 for winding the substrate 1, and guide rolls 14a to 14d. The substrate 1 sent out from the substrate transport mechanism 11A is then transported by a pretreatment roller 20 (described later) arranged in the plasma pretreatment chamber 12B and a film formation roller 25 (described later) arranged in the film formation chamber 12C.

[0087] Although not shown, the substrate transport mechanism 11A may further include a tension pick-up roller. By including the tension pick-up roller in the substrate transport mechanism 11A, the substrate 1 can be transported while adjusting the tension applied to the substrate 1.

[0088] (Plasma pretreatment mechanism) The plasma pretreatment mechanism 11B will be described. The plasma pretreatment mechanism 11B is a mechanism for performing plasma pretreatment on the surface of the substrate 1. The plasma pretreatment mechanism 11B shown in FIG. 2 generates plasma P and performs plasma pretreatment on the surface of the substrate 1 using the generated plasma P. When the surface of the substrate 1 is activated by plasma pretreatment, for example, hydrogen is released from the substrate resin component to generate carbon radicals. Then, functional groups such as hydroxyl groups, carboxyl groups, and ketone groups are generated by bonding with oxygen and hydrogen in the atmosphere. It is believed that the generation of such functional groups improves the adhesion between the substrate 1 and the deposition film. The plasma pretreatment mechanism 11B shown in FIG. 2 has a pretreatment roller 20 arranged in the plasma pretreatment chamber 12B, an electrode unit 21 facing the pretreatment roller 20, and a magnetic field forming unit 23 that forms a magnetic field between the pretreatment roller 20 and the electrode unit 21.

[0089] The pretreatment roller 20 will be described. FIG. 3 is an enlarged view of the portion surrounded by the dashed line marked with the symbol VI in FIG. 2. Note that in FIG. 3, the power supply wiring 31 connecting the power source 32 shown in FIG. 2 and the electrode unit 21 described later, and the plasma P generated by the plasma pretreatment mechanism 11B are omitted. The pretreatment roller 20 has a rotation axis X. The pretreatment roller 20 is provided so that at least the rotation axis X is located in the plasma pretreatment chamber 12B partitioned by the partition walls 35a and 35b. The substrate 1 having a dimension in the direction of the rotation axis X is wound around the pretreatment roller 20. In the following description, the dimension of the substrate 1 in the direction of the rotation axis X is also referred to as the width of the substrate 1. The direction of the rotation axis X is also referred to as the width direction of the substrate 1.

[0090] As shown in FIG. 2, the pretreatment roller 20 may be provided so that a part of it is exposed to the substrate transport chamber 12A side. In the example shown in FIG. 2, the plasma pretreatment chamber 12B and the substrate transport chamber 12A are connected through an opening provided in the partition wall 35a, and a part of the pretreatment roller 20 is exposed to the substrate transport chamber 12A side through the opening. A gap is provided between the partition wall 35a between the substrate transport chamber 12A and the plasma pretreatment chamber 12B and the pretreatment roller 20, and the substrate 1 can be transported from the substrate transport chamber 12A to the plasma pretreatment chamber 12B through the gap. Although not shown, the pretreatment roller 20 may be provided so that the entirety thereof is located within the plasma pretreatment chamber 12B.

[0091] Although not shown, the pretreatment roller 20 may have a temperature adjustment mechanism that adjusts the surface temperature of the pretreatment roller 20. For example, the pretreatment roller 20 may have a temperature adjustment mechanism inside the pretreatment roller 20 that includes piping for circulating a temperature adjustment medium such as a refrigerant or a heat medium. The temperature adjustment mechanism adjusts the surface temperature of the pretreatment roller 20 to a target temperature within a range of, for example, −20° C. or more and 100° C. or less.

[0092] By providing the pretreatment roller 20 with a temperature adjustment mechanism, it is possible to prevent the substrate 1 from shrinking or being damaged by heat during plasma pretreatment.

[0093] The pretreatment roller 20 is made of a material containing at least one of stainless steel, iron, copper, and chromium. The surface of the pretreatment roller 20 may be treated with a hard chrome hard coat to prevent scratches. These materials are easy to process. In addition, by using the above materials as the material for the pretreatment roller 20, the thermal conductivity of the pretreatment roller 20 itself is increased, making it easier to control the temperature of the pretreatment roller 20.

[0094] The electrode unit 21 will be described. In the example shown in FIG. 2 and FIG. 3, the electrode unit 21 has a first surface 21c facing the pretreatment roller 20 and a second surface 21d located on the opposite side of the first surface 21c. In the example shown in FIG. 2 and FIG. 3, the electrode unit 21 is a plate-shaped member, and both the first surface 21c and the second surface 21d are flat. The electrode unit 21 generates plasma between the pretreatment roller 20 by applying an AC voltage between the electrode unit 21 and the pretreatment roller 20. The electrode unit 21 preferably forms an electric field between the electrode unit 21 and the pretreatment roller 20 so that the generated plasma moves in a direction perpendicular to the surface of the substrate 1 toward the surface of the substrate 1. This allows the substrate 1 to be pretreated efficiently.

[0095] The number of electrode portions 21 is preferably 2 or more. The two or more electrode portions 21 are preferably arranged along the transport direction of the substrate 1. In the example shown in Fig. 2 and Fig. 3, an example is shown in which the film forming apparatus 10 has two electrode portions 21. In addition, the number of electrode portions 21 is, for example, 12 or less.

[0096] The effect of two or more electrode sections 21 arranged along the transport direction of the substrate 1 will be described. As described above, plasma is generated between the electrode section 21 and the pretreatment roller 20. The region in which plasma is generated expands as the dimension of the electrode section 21 in the transport direction increases. On the other hand, when the electrode section 21 is a flat plate-like member, the larger the dimension of the electrode section 21 in the transport direction, the greater the distance from the end of the first surface 21c, which is the surface of the electrode section 21 facing the pretreatment roller 20, to the pretreatment roller 20 in the transport direction, which reduces the processing ability by plasma.

[0097] In the film forming apparatus 10, two or more electrode units 21 are arranged along the transport direction of the substrate 1. Therefore, even if the dimension of the electrode unit 21 in the transport direction of the substrate 1 is small, plasma can be generated over a wide range in the transport direction. Furthermore, by reducing the dimension of the electrode unit 21, the distance from the end of the first surface 21c of the electrode unit 21 to the pretreatment roller 20 in the transport direction can be reduced, and plasma can be generated uniformly in the transport direction.

[0098] As shown in FIG. 2 and FIG. 3, the electrode unit 21 has a first end 21e and a second end 21f located on the first surface 21c of the electrode unit 21. The first end 21e is an end on the upstream side in the conveying direction of the substrate 1, and the second end 21f is an end on the downstream side in the conveying direction of the substrate 1. As described above, by reducing the dimension of the electrode unit 21 in the conveying direction of the substrate 1, the distance from the first end 21e and the second end 21f of the electrode unit 21 to the pre-treatment roller 20 in the conveying direction can be reduced. The dimension of the electrode unit 21 in the conveying direction of the substrate 1 corresponds to the angle θ shown in FIG. 3. The angle θ is the angle formed by a straight line passing through the first end 21e and the rotation axis X and a straight line passing through the second end 21f and the rotation axis X. The angle θ is preferably 20° or more and 90° or less, more preferably 60° or less, and even more preferably 45° or less. When the angle θ is within the above range, plasma can be generated uniformly in the transport direction between the electrode unit 21 and the pretreatment roller 20 when the first surface 21c of the electrode unit 21 is a flat surface.

[0099] There are no particular limitations on the material of the electrode portion 21 as long as it is conductive. Specifically, aluminum, copper, and stainless steel are preferably used as the material of the electrode portion 21.

[0100] The thickness L3 of the electrode unit 21 when viewed in a direction perpendicular to the first surface 21c of the electrode unit 21 is not particularly limited, but is, for example, 15 mm or less. When the thickness of the electrode unit 21 is the above value, a magnetic field can be effectively formed between the pre-treatment roller 20 and the electrode unit 21 by the magnetic field forming unit 23. The thickness L3 of the electrode unit 21 is, for example, 3 mm or more.

[0101] The magnetic field forming unit 23 will be described. As shown in Figs. 2 and 3, the magnetic field forming unit 23 is provided on the side of the electrode unit 21 opposite to the side facing the pretreatment roller 20. The magnetic field forming unit 23 is a member that forms a magnetic field between the pretreatment roller 20 and the electrode unit 21. The magnetic field between the pretreatment roller 20 and the electrode unit 21 contributes to the generation of higher density plasma, for example, when plasma is generated using the plasma pretreatment mechanism 11B. The magnetic field forming unit 23 shown in Figs. 2 and 3 has a first magnet 231 and a second magnet 232 provided on the second surface 21d of the electrode unit 21.

[0102] The number of the magnetic field forming units 23 is preferably 2 or more. When the plasma pretreatment mechanism 11B has two or more electrode units 21 and two or more magnetic field forming units 23, each of the two or more magnetic field forming units 23 is preferably provided on the side of each of the two or more electrode units 21 opposite to the side facing the pretreatment roller 20. In the example shown in Figures 2 and 3, each of the two magnetic field forming units 23 is provided on the second surface 21d of each of the two electrode units 21.

[0103] The structure of the first magnet 231 and the second magnet 232 in the normal direction of the second surface 21d of the electrode unit 21 will be described. As shown in FIG. 2 and FIG. 3, the first magnet 231 and the second magnet 232 each have an N pole and an S pole. The symbol N shown in FIG. 2 and FIG. 3 indicates the N pole of the first magnet 231 or the second magnet 232. Also, the symbol S shown in FIG. 2 and FIG. 3 indicates the S pole of the first magnet 231 or the second magnet 232. One of the N pole or S pole of the first magnet 231 is located closer to the substrate 1 than the other. Also, the other of the N pole or S pole of the second magnet 232 is located closer to the substrate 1 than the other. In the example shown in FIG. 2 and FIG. 3, the N pole of the first magnet 231 is located closer to the substrate 1 than the S pole of the first magnet 231, and the S pole of the second magnet 232 is located closer to the substrate 1 than the N pole of the second magnet. Although not shown, the south pole of first magnet 231 may be located closer to substrate 1 than the north pole of first magnet 231, and the north pole of second magnet 232 may be located closer to substrate 1 than the south pole of second magnet 232.

[0104] Next, the structures of the first magnet 231 and the second magnet 232 in the planar direction of the second surface 21d of the electrode unit 21 will be described. Fig. 4 is a plan view of the electrode unit 21 and the magnetic field forming unit 23 shown in Fig. 2, viewed from the magnetic field forming unit 23 side. Fig. 5 is a cross-sectional view showing a cross section taken along line VIII-VIII in Fig. 4. In Fig. 4, direction D1 is the direction in which the rotation axis X of the pre-treatment roller 20 extends.

[0105] As shown in Figures 4 and 5, the first magnet 231 has a first axial portion 231c. As shown in Figure 4, the first axial portion 231c extends along the direction D1, i.e., along the rotation axis X of the pre-treatment roller 20. The first magnet 231 provided in one electrode unit 21 may have one first axial portion 231c, or may have two or more first axial portions 231c. In the example shown in Figure 4, the first magnet 231 provided in one electrode unit 21 has one first axial portion 231c.

[0106] 4 and 5, the second magnet 232 has a second axial portion 232c. As shown in Fig. 4, the second axial portion 232c also extends along the direction D1, i.e., along the rotation axis X, similar to the first axial portion 231c.

[0107] Since both the first magnet 231 and the second magnet 232 include a portion extending along the rotation axis X, it is possible to increase the uniformity of the strength of the magnetic field formed around the substrate 1 in the width direction of the substrate 1. This makes it possible to increase the uniformity of the distribution density of the plasma formed around the substrate 1 in the width direction of the substrate 1.

[0108] The second magnet 232 provided on one electrode unit 21 may have one second axial portion 232c, or may have two or more second axial portions 232c. In the example shown in Fig. 4 and Fig. 5, the second magnet 232 provided on one electrode unit 21 has two second axial portions 232c. The two second axial portions 232c may be positioned so as to sandwich the first axial portion 231c in a direction D2 perpendicular to the rotation axis X in the planar direction of the second surface 21d of the electrode unit 21.

[0109] 5, the dimension L4 of the first axial portion 231c and the dimension L5 of the second axial portion 232c in the transport direction of the base material 1 are not particularly limited. In addition, the ratio of the dimension L4 of the first axial portion 231c to the dimension L5 of the second axial portion 232c in the transport direction of the base material 1 is not particularly limited. The dimension L4 of the first axial portion 231c and the dimension L5 of the second axial portion 232c may be equal, or the dimension L4 of the first axial portion 231c may be larger than the dimension L5 of the second axial portion 232c.

[0110] The distance L6 between the first axial portion 231c and the second axial portion 232c in the direction D2 is set so that a magnetic field generated by the first axial portion 231c and the second axial portion 232c is formed between the pre-treatment roller 20 and the electrode portion 21.

[0111] The second magnet 232 may surround the first magnet 231 when the magnetic field generating unit 23 is viewed along the normal direction of the second surface 21d of the electrode unit 21. For example, as shown in Fig. 4, the second magnet 232 may have two second axial portions 232c as well as two connection portions 232d provided to connect the two second axial portions 232c.

[0112] Examples of the types of magnets used as the magnetic field forming unit 23, such as the first magnet 231 and the second magnet 232, include permanent magnets such as ferrite magnets and rare earth magnets such as neodymium and samarium cobalt (samarium cobalt). Also, an electromagnet can be used as the magnetic field forming unit 23.

[0113] The magnetic flux density of the magnets of the magnetic field forming unit 23, such as the first magnet 231 and the second magnet 232, is, for example, 100 Gauss or more and 10,000 Gauss or less. If the magnetic flux density is 100 Gauss or more, a sufficiently strong magnetic field can be formed between the pretreatment roller 20 and the electrode unit 21, thereby generating plasma with a sufficiently high density, and a good pretreatment surface can be formed at high speed. On the other hand, in order to increase the magnetic flux density on the surface of the substrate 1 to more than 10,000 Gauss, an expensive magnet or magnetic field generating mechanism is required.

[0114] Although not shown, the plasma pretreatment mechanism 11B may have a plasma raw material gas supply unit. The plasma raw material gas supply unit supplies a gas serving as a raw material for plasma into the plasma pretreatment chamber 12B. The configuration of the plasma raw material gas supply unit is not particularly limited. For example, the plasma raw material gas supply unit is provided on the wall surface of the plasma pretreatment chamber 12B and includes a hole for ejecting the gas serving as a raw material for plasma. The plasma raw material gas supply unit may have a nozzle for ejecting the plasma raw material gas at a position closer to the substrate 1 than the wall surface of the plasma pretreatment chamber 12B. The plasma raw material gas supplied by the plasma raw material gas supply unit may be, for example, an inert gas such as argon, an active gas such as oxygen, nitrogen, carbon dioxide, or ethylene, or a mixed gas of these gases. As the plasma raw material gas, one kind of inert gas may be used alone, one kind of active gas may be used alone, or a mixed gas of two or more kinds of gases contained in the inert gas or active gas may be used. As the plasma raw material gas, a mixed gas of an inert gas such as argon and an active gas may be used. As an example, the plasma raw material gas supply unit supplies a mixed gas of argon (Ar) and oxygen (O2).

[0115] The plasma pretreatment mechanism 11B has a plasma density of, for example, 100 W·sec / m 2 More than 8000W sec / m 2 The following plasma is supplied between the pretreatment roller 20 and the electrode unit 21.

[0116] 2, the plasma pretreatment mechanism 11B is disposed in a plasma pretreatment chamber 12B separated by a partition from the substrate transport chamber 12A and the film formation chamber 12C. By separating the plasma pretreatment chamber 12B from other regions such as the substrate transport chamber 12A and the film formation chamber 12C, it becomes easier to adjust the atmosphere in the plasma pretreatment chamber 12B independently. This makes it easier to control the plasma raw material gas concentration in the space where the pretreatment roller 20 and the electrode unit 21 face each other, improving the productivity of the laminated film.

[0117] (Film forming mechanism) Next, the film formation mechanism 11C will be described. In the example shown in Fig. 2, the film formation mechanism 11C includes a film formation roller 25 and an evaporation mechanism 24 disposed in a film formation chamber 12C.

[0118] The film-forming roller 25 will be described below. The film-forming roller 25 is a roller that wraps around and transports the substrate 1 with the treated surface of the substrate 1 that has been pretreated in the plasma pretreatment mechanism 11B facing outward.

[0119] The material of the film-forming roller 25 will be described. The film-forming roller 25 is preferably formed from a material containing at least one of stainless steel, iron, copper, and chromium. The surface of the film-forming roller 25 may be subjected to a hard chrome hard coat treatment or the like to prevent scratches. These materials are easy to process. In addition, by using the above-mentioned materials as the material of the film-forming roller 25, the thermal conductivity of the film-forming roller 25 itself is increased, so that the temperature controllability is excellent when performing temperature control. The surface average roughness Ra of the film-forming roller 25 is, for example, 0.1 μm or more and 10 μm or less.

[0120] Although not shown, the film-forming roller 25 may have a temperature adjustment mechanism for adjusting the temperature of the surface of the film-forming roller 25. The temperature adjustment mechanism has, for example, a circulation path for circulating a cooling medium or a heat source medium inside the film-forming roller 25. The cooling medium (coolant) is, for example, an ethylene glycol aqueous solution, and the heat source medium (heat medium) is, for example, silicone oil. The temperature adjustment mechanism may have a heater installed at a position facing the film-forming roller 25. When the film-forming mechanism 11C forms a film by a deposition method, the temperature adjustment mechanism preferably adjusts the surface temperature of the film-forming roller 25 to a target temperature within a range of -20°C to 200°C in terms of restrictions on the heat resistance of related mechanical parts and versatility. By having the temperature adjustment mechanism in the film-forming roller 25, it is possible to suppress the temperature fluctuation of the substrate 1 caused by the heat generated during film formation.

[0121] The evaporation mechanism 24 will be described. FIG. 6 is an enlarged view of the portion surrounded by the dashed line marked with the symbol IX in FIG. 2, showing a specific form of the evaporation mechanism 24 that was omitted in FIG. 5, and showing an evaporation material supply unit 61 that supplies an evaporation material that was omitted in FIG. 2. Note that the decompression chamber 12 and the partition walls 35b and 35c are omitted in FIG. 6. The evaporation mechanism 24 is a mechanism that evaporates an evaporation material containing aluminum. The evaporated evaporation material adheres to the substrate 1, so that an evaporation film containing aluminum is formed on the surface of the substrate 1. The evaporation mechanism 24 in this embodiment employs a resistance heating type. In the example shown in FIG. 6, the evaporation mechanism 24 has a boat 24b. In this embodiment, the boat 24b has a power source (not shown) and a resistor (not shown) electrically connected to the power source. A plurality of boats 24b may be arranged in the width direction of the substrate 1.

[0122] As shown in Fig. 6, the film formation mechanism 11C may have a deposition material supply unit 61 that supplies a deposition material to the evaporation mechanism 24. Fig. 6 shows an example in which the deposition material supply unit 61 continuously feeds out an aluminum metal wire.

[0123] Although not shown, the film formation mechanism 11C has a gas supply mechanism. The gas supply mechanism is a mechanism that supplies gas between the evaporation mechanism 24 and the film formation roller 25. The gas supply mechanism supplies at least oxygen gas. The oxygen gas reacts with or bonds with an evaporation material such as aluminum that has evaporated from the evaporation mechanism 24 and is heading toward the substrate 1 on the film formation roller 25. This allows a vapor deposition film containing aluminum oxide to be formed on the surface of the substrate 1.

[0124] The film forming mechanism 11C also includes a plasma supply mechanism 50 that supplies plasma between the surface of the substrate 1 and the evaporation mechanism 24. In the example shown in FIG. 2 and FIG. 6, the plasma supply mechanism 50 has a hollow cathode 51. In this embodiment, the hollow cathode 51 is a cathode having a hollow portion that is partially open. The hollow cathode 51 can generate plasma in the hollow portion. In the example shown in FIG. 6, the hollow cathode 51 is provided so that the opening of the hollow portion of the hollow cathode 51 is located diagonally above the boat 24b. Although not shown, the plasma supply mechanism 50 according to this embodiment has an anode facing the opening, which draws out plasma from the opening of the hollow portion of the hollow cathode 51. The plasma supply mechanism 50 according to this embodiment can generate strong plasma between the surface of the substrate 1 and the evaporation mechanism 24 by generating plasma in the hollow portion of the hollow cathode 51 and drawing the plasma between the surface of the substrate 1 and the evaporation mechanism 24 by the opposing anode. The position of the opposing anodes is not particularly limited as long as the opposing anodes can draw out plasma from the opening of the cavity of the hollow cathode 51 and supply plasma between the surface of the substrate 1 and the evaporation mechanism 24. In this embodiment, a case where the opposing anodes are arranged on both sides of the boat 24b in the width direction of the substrate 1 will be described. In this case, the film formation mechanism 11C has a plurality of boats 24b and a plurality of opposing anodes, and the plurality of boats 24b and the plurality of opposing anodes may be arranged alternately in the width direction of the substrate 1. Although not shown, the plasma supply mechanism 50 may have a raw material supply device that supplies plasma raw material gas at least into the cavity of the hollow cathode 51. As the plasma raw material gas supplied by the raw material supply device, for example, a gas similar to the gas that can be used as the plasma raw material gas supplied by the plasma raw material gas supply unit of the plasma pretreatment mechanism 11B can be used.

[0125] By performing plasma assist during deposition by supplying plasma between the surface of the substrate 1 and the evaporation mechanism 24 using the plasma supply mechanism 50, the aluminum and oxygen gas evaporated in the evaporation mechanism 24 can be activated, and the reaction or bonding between the aluminum and the oxygen gas can be promoted. This can increase the ratio of aluminum present as aluminum oxide in the evaporated film formed on the surface of the substrate 1, and stabilize the properties of the evaporated film.

[0126] Although not shown, the film forming apparatus 10 may include a substrate charge removal unit that performs post-processing to remove charge generated on the substrate 1 due to film formation by the film formation mechanism 11C, in a portion of the substrate transport chamber 12A that is located downstream of the film formation chamber 12C in the transport direction of the substrate 1. The substrate charge removal unit may be provided so as to remove charge from one side of the substrate 1, or may be provided so as to remove charge from both sides of the substrate 1.

[0127] The device used as the substrate charge removal section for performing post-treatment on the substrate 1 is not particularly limited, but for example, a plasma discharge device, an electron beam irradiation device, an ultraviolet ray irradiation device, a static elimination bar, a glow discharge device, a corona treatment device, etc. can be used.

[0128] When performing post-treatment by forming a discharge using a plasma treatment device or a glow discharge device, a discharge gas such as argon, oxygen, nitrogen, helium, or a mixture of these gases is supplied near the substrate 1, and post-treatment can be performed using any discharge method such as alternating current (AC) plasma, direct current (DC) plasma, arc discharge, microwave, surface wave plasma, etc. In a reduced pressure environment, it is most preferable to perform post-treatment using a plasma discharge device.

[0129] The substrate charge removal section is provided in a portion of the substrate transport chamber 12A that is located downstream of the film formation chamber 12C in the transport direction of the substrate 1, and the charge on the substrate 1 is removed, so that the substrate 1 can be transported by quickly separating it from the film formation roller 25 at a predetermined position. This enables stable substrate transport, prevents damage to the substrate 1 or deterioration in quality due to charging, and improves post-processing suitability by improving the wettability of the front and back surfaces of the substrate.

[0130] (power supply) In the example shown in FIG. 2, the film forming apparatus 10 further includes a power source 32 electrically connected to the pretreatment roller 20 and the electrode unit 21. In the example shown in FIG. 5, the power source 32 is electrically connected to the pretreatment roller 20 and the electrode unit 21 via the power supply wiring 31. The power source 32 is, for example, an AC power source. When the power source 32 is an AC power source, the power source 32 can apply an AC voltage having a frequency of, for example, 20 kHz or more and 500 kHz or less between the pretreatment roller 20 and the electrode unit 21. The input power that can be applied by the power source 32 (power that can be applied per 1 m width of the electrode unit 21 in the width direction of the substrate 1) is not particularly limited, but is, for example, 0.5 kW / m or more and 20 kW / m or less. The pretreatment roller 20 may be installed at an electrically earth level or at an electrically floating level.

[0131] (Barrier film manufacturing method) Next, a method for manufacturing the barrier film shown in FIG. 1 using the above-mentioned film forming apparatus 10 will be described. First, a first film forming step (hereinafter also simply referred to as a film forming step) of forming a first vapor deposition film on the surface of the substrate 1 will be described. In film formation using the film forming apparatus 10, a plasma pretreatment step of performing plasma pretreatment on the surface of the substrate 1 using the plasma pretreatment mechanism 11B and a film forming step of forming a vapor deposition film on the surface of the substrate 1 using the film forming mechanism 11C are performed while the substrate 1 is transported along the above-mentioned transport path of the substrate 1. The transport speed of the substrate 1 is preferably 200 m / min or more, more preferably 400 m / min or more and 1000 m / min or less.

[0132] (Plasma pretreatment process) The plasma pretreatment step is carried out, for example, by the following method. First, plasma raw material gas is supplied into the plasma pretreatment chamber 12B. Next, the above-mentioned AC voltage is applied between the pretreatment roller 20 and the electrode unit 21. When applying the AC voltage, input power control or impedance control may be performed.

[0133] The plasma raw material gas supplied in the pretreatment is oxygen alone or a mixture of oxygen gas and an inert gas, which is supplied from a gas reservoir while measuring the flow rate of the gas through a flow rate controller. The inert gas may be one or a mixture of two or more gases selected from the group consisting of argon, helium, and nitrogen.

[0134] In the plasma treatment, the mixing ratio of oxygen gas to the inert gas, that is, oxygen gas / inert gas, is preferably 6 / 1 to 1 / 1, and more preferably 5 / 2 to 3 / 2.5.

[0135] By setting the mixing ratio to 6 / 1 to 1 / 1, the energy required for forming the evaporated aluminum film on the resin substrate is increased, and by setting it to 5 / 2 to 3 / 2, the degree of oxidation of the evaporated aluminum oxide film is increased, thereby ensuring adhesion between the evaporated aluminum oxide film and the substrate 1.

[0136] Application of the AC voltage generates plasma simultaneously with glow discharge, and plasma P is densified between pretreatment roller 20 and magnetic field forming unit 23. In this manner, plasma P can be supplied between pretreatment roller 20 and magnetic field forming unit 23. This plasma P can be used to perform plasma (ion) pretreatment on the surface of substrate 1.

[0137] Plasma intensity per unit area in plasma processing is 50 W·sec / m 2 More than 8000W sec / m 2 Less than 50W sec / m 2 Below this, no effect of plasma pretreatment was observed, and below 8000W·sec / m 2Above this level, the resin substrate tends to deteriorate due to the plasma, such as wear, damage, discoloration, and burning. In particular, the plasma intensity for plasma pretreatment to form an aluminum oxide layer should be 100 W sec / m 2 More than 1000W sec / m 2 The following is preferred:

[0138] The pressure in plasma pretreatment chamber 12B when an AC voltage is applied between pretreatment roller 20 and electrode unit 21 is reduced to below atmospheric pressure by decompression chamber 12. In this case, the pressure in plasma pretreatment chamber 12B is adjusted, for example, so that a glow discharge can be generated between pretreatment roller 20 and electrode unit 21 by application of an AC voltage. The pressure in plasma pretreatment chamber 12B when an AC voltage is applied between pretreatment roller 20 and electrode unit 21 can be set and maintained at about 0.1 Pa or more and 100 Pa or less, and is particularly preferably 1 Pa or more and 20 Pa or less.

[0139] The function of the magnetic field forming unit 23 in the plasma pretreatment step will now be described. The magnetic field forming unit 23 forms a magnetic field between the pretreatment roller 20 and the electrode unit 21. The magnetic field can act to capture and accelerate electrons present between the pretreatment roller 20 and the electrode unit 21. As a result, in the region where the magnetic field is formed, it is possible to increase the frequency of collisions between the electrons and the plasma raw material gas, increase the density of the plasma, and localize it, thereby improving the efficiency of the plasma pretreatment.

[0140] (First film forming process) In the film formation step, a film is formed using film formation mechanism 11C on the surface of substrate 1. As an example of the film formation step, a case will be described in which an aluminum oxide vapor deposition film is formed using film formation mechanism 11C having evaporation mechanism 24 shown in FIG.

[0141] First, a deposition material containing aluminum is supplied into the boat 24b of the evaporation mechanism 24 so as to face the deposition roller 25. An aluminum metal wire can be used as the deposition material. In the example shown in Fig. 6, the deposition material is supplied to the boat 24b by continuously feeding the aluminum metal wire into the boat 24b using a deposition material supply unit 61.

[0142] The aluminum is evaporated in the boat 24b by heating. For convenience, FIG. 6 shows evaporated aluminum vapor 63. The oxygen gas for oxidizing the aluminum may be supplied as oxygen alone or as a mixed gas with an inert gas such as argon, but by controlling the amount of oxygen, both barrier properties and transparency can be achieved. The pressure at this time is preferably 0.05 Pa or more and 8.00 Pa or less.

[0143] Furthermore, a method for supplying plasma between the surface of the substrate 1 and the evaporation mechanism 24 by the plasma supply mechanism 50, i.e., plasma assist during deposition, will be described. In this embodiment, plasma is generated within the cavity of the hollow cathode 51 of the plasma supply mechanism 50. Next, a discharge is generated between the hollow cathode 51 and the opposing anode, and the plasma within the cavity of the hollow cathode 51 is drawn between the surface of the substrate 1 and the evaporation mechanism 24.

[0144] In this embodiment, the discharge generated between hollow cathode 51 and the opposing anode is an arc discharge. The arc discharge means a discharge with a current value of, for example, 10 A or more.

[0145] By evaporating aluminum while supplying plasma between the surface of the substrate 1 and the evaporation mechanism 24, plasma is supplied to the aluminum vapor 63. Supplying plasma can promote the reaction or bonding between the aluminum vapor 63 and oxygen gas. This allows the aluminum vapor 63 to be oxidized before it reaches the surface of the substrate 1. The evaporated and oxidized aluminum adheres to the substrate 1, forming an aluminum oxide vapor deposition film on the surface of the substrate 1, and the barrier film shown in FIG. 1 can be manufactured.

[0146] The plasma raw material gas supplied by the plasma supply mechanism 50 is preferably argon gas.

[0147] In this embodiment, a plasma pretreatment step is performed before the film formation step, in which plasma is supplied to the surface of the substrate 1. In the plasma pretreatment step, an AC voltage is applied between the electrode unit 21 and the pretreatment roller 20. In addition, a magnetic field is generated in the space between the electrode unit 21 and the pretreatment roller 20 by using the magnetic field forming unit 23 located on the side of the surface of the electrode unit 21 opposite to the surface facing the pretreatment roller 20. Therefore, plasma can be efficiently generated in the space between the electrode unit 21 and the pretreatment roller 20, and the plasma can be made to perpendicularly enter the surface of the substrate 1 wound around the pretreatment roller 20. Therefore, the adhesion between the film formed in the film formation step and the substrate 1 can be improved.

[0148] (Aging treatment after film formation process) The barrier film roll that has been subjected to the above-mentioned film-forming process is then subjected to an aging treatment (heating treatment) for a predetermined period of time, which promotes the introduction of hydroxyl groups into the vapor-deposited aluminum oxide film, forming a vapor-deposited film with excellent barrier properties, particularly excellent water vapor barrier properties.

[0149] The aging temperature is preferably 50° C. or higher and 60° C. or lower. The lower limit of the aging time is 24 hours (1 day) or higher, more preferably 48 hours (2 days) or higher. The upper limit is 144 hours (6 days) or lower, more preferably 96 hours (4 days) or lower. The aging humidity is not particularly limited, but does not need to be high, and may be normal relative humidity of 40% or higher and 70% or lower.

[0150] (First coating layer forming process) In the first coating layer forming step (hereinafter also simply referred to as the coating layer forming step), the first coating layer can be manufactured by the following method. First, the above metal alkoxide, water-soluble polymer, silane coupling agent added as necessary, sol-gel catalyst, acid, and organic solvent such as water as a solvent, methyl alcohol, ethyl alcohol, isopropanol, etc., are mixed to prepare a barrier coating agent. Next, the above barrier coating agent is applied on the aluminum oxide vapor deposition film by a conventional method and dried. This drying step further advances polycondensation of silanols generated from the above metal alkoxide and silane coupling agent to form a coating film. The drying conditions include a temperature of 20 to 200°C and below the melting point of the plastic substrate 1, preferably a temperature in the range of 50 to 180°C, and a heat treatment for 3 seconds to 10 minutes. This allows a coating layer of the above barrier coating agent to be formed on the aluminum oxide vapor deposition film. The above coating operation may be further repeated on the first coating film to form a plurality of coating films consisting of two or more layers.

[0151] The barrier film roll that has been subjected to the above-mentioned coating layer forming step is subjected to an aging treatment (heating treatment) for a predetermined period of time, which allows the condensation of the coating layer to proceed appropriately, thereby obtaining a barrier film whose barrier properties are resistant to deterioration.

[0152] The lower limit of the aging temperature after the coating layer forming step is preferably 40°C or higher, more preferably 50°C or higher. The upper limit is preferably 100°C or lower, more preferably 70°C or lower. The lower limit of the aging time is 24 hours (1 day) or higher, more preferably 48 hours (2 days) or higher. The upper limit is 144 hours (6 days) or lower, more preferably 96 hours (4 days) or lower. The aging humidity is not particularly limited, but does not need to be high, and may be normal relative humidity of 40% or higher and 70% or lower.

[0153] (Second film forming process) An aluminum oxide deposition film is further formed on the first coating layer to form the second deposition film 132b in Fig. 1. This deposition can be performed under the same conditions as the plasma pretreatment process, the first deposition process, and the aging process. The first and second deposition films may be formed under the same conditions or different conditions.

[0154] (Second coating layer forming process) Furthermore, the second coating layer 132a in FIG. 1 is formed on the aluminum oxide deposition film deposited through the second film formation process. The film formation can be performed under the same conditions as the first coating layer formation process. The first and second coating layers may be formed under the same conditions or different conditions.

[0155] <<Laminate>> Next, the laminate of the present invention using a barrier film will be described. The laminate 100B in Fig. 7 is an example showing a laminate using the barrier film in Fig. 1. Compared to the barrier film 100A in Fig. 1, a matte layer 160 is formed on the surface of the substrate 120 opposite to the first vapor-deposited film 131b. The laminate of the present invention is suitably used for a wavelength conversion sheet, etc.

[0156] 8, the substrate 120 of the barrier film 100A and the support 150 are laminated via a pressure-sensitive adhesive or adhesive layer 140 (hereinafter referred to as the tacky adhesive layer 140). The matte layer 160 is formed on the surface of the support 150 opposite to the barrier film 100A.

[0157] 9, the barrier layer 130 of the barrier film 100A and the support 150 are laminated via a pressure-sensitive adhesive layer or adhesive layer 140 (hereinafter referred to as the adhesive layer 140). That is, it differs from FIG. 8 in that the barrier film 100A is arranged in the opposite direction.

[0158] In this way, the matte layer 160 may be formed on the surface of the base material 120 opposite to the first aluminum oxide vapor-deposited film 131b. Specifically, the matte layer 160 may be formed on one surface of the base material 120. In this case, this includes not only the case where the matte layer is formed directly on the surface, but also the case where the matte layer is formed via a primer layer or the like. The matte layer 160 may also be formed on one surface of the base material 120 via another support 150 or the like.

[0159] Hereinafter, each layer constituting the laminates 100B, 100C, and 100D will be described.

[0160] [Matte layer] The matte layer 160 is a layer having an uneven surface, and is, for example, an anti-sticking layer or a light diffusing layer. The matte layer can effectively prevent the wavelength conversion sheet from sticking to the light guide plate 330, the diffusion plate 370, etc., and can diffuse the light incident on and emitted from the wavelength conversion sheet, thereby further increasing the light wavelength conversion efficiency.

[0161] 7 to 9, mat layer 160 is a layer containing resin 161 and particles 162, and the surface of this mat layer 160 has an uneven surface shape due to the particles contained in the mat layer, at least some of the particles protruding. Here, the phrase "mat layer with at least some of the particles protruding" means that the surface of the mat layer is not uniformly flat, but the particles form undulations on the surface of the mat layer and / or at least some of the particles are exposed from the surface of the mat layer.

[0162] As long as the surface can be formed with an uneven shape, the matte layer may be in an embodiment that does not contain particles.

[0163] <Anti-sticking layer> When the matte layer 160 is an anti-sticking layer, it is possible to effectively prevent the wavelength conversion sheet from sticking to the light guide plate 330, the diffusion plate 370, etc., and also to prevent chipping of the convex parts of the prism sheet 340 due to rubbing.

[0164] Furthermore, by providing the barrier film with an anti-sticking layer, the barrier films or wavelength-converting sheets can be prevented from sticking to each other when rolled up, which makes it possible to store or transport the barrier films or wavelength-converting sheets in a roll.

[0165] In particular, when a display device having a light guide plate disposed on the surface of the stick-prevention layer of the wavelength conversion sheet is transported, the stick-prevention layer may rub against the light guide plate, causing scratches on the stick-prevention layer. Alternatively, the stick-prevention layer may rub against the light guide plate, causing fragments to be generated from the stick-prevention layer, which may damage the stick-prevention layer or the light guide plate. Such scratches on the stick-prevention layer or the light guide plate may cause a defective appearance of the display device.

[0166] Therefore, in the laminate according to the present embodiment, the ratio of particles protruding from the adhesion-preventing layer that are twice or more as large as the thickness of the adhesion-preventing layer, that is, the ratio of particles protruding from the adhesion-preventing layer that are visually recognized as having a diameter twice or more as the thickness of the adhesion-preventing layer in a plan view of the adhesion-preventing layer, is preferably 20% to 80% of the total amount of particles protruding from the adhesion-preventing layer. If the ratio of these particles is less than 20%, the scratch resistance of the mat layer may be deteriorated, and furthermore, the adhesion between the wavelength conversion sheet and the light guide plate or the like may not be effectively suppressed. In addition, if the ratio of these particles is more than 80%, the scratch resistance of the mat layer may be deteriorated. Here, the thickness of the adhesion-preventing layer refers to the thickness of the layer of the resin 161 that constitutes the adhesion-preventing layer.

[0167] The laminate according to the present embodiment has a thickness of 1 mm in plan view of the sticking prevention layer. 2 It is preferable that the total number of particles in the square is 1800 or more. This may effectively prevent the wavelength conversion sheet from sticking to the light guide plate or the like, and may improve the scratch resistance of the sticking-prevention layer. 2 The upper limit of the total number of particles within the square is not particularly limited, but for example, it is preferably 20,000 or less, and more preferably 15,000 or less. 2 The total number of particles within the square refers to the total number of particles exposed on the surface of the adhesion preventing layer when the adhesion preventing layer is viewed from the front side, and does not include the number of particles that are buried in the adhesion preventing layer and cannot be seen from the front.

[0168] The proportion of particles visually recognized as having a particle size twice or more can be measured, for example, by observing the surface of the anti-adhesive layer of a predetermined area (e.g., 258 × 260 μm) in a plan view using a microscope (e.g., a laser microscope or a scanning electron microscope) or a microscope. If necessary, the measurement screen is adjusted so that the planar portion is horizontal. An image is then obtained, and the brightness is adjusted so that the particle portion can be extracted. The particles and their diameters are calculated from the image with the adjusted brightness. The proportion of particles visually recognized as having a particle size twice or more the thickness of the anti-adhesive layer is then calculated from the thickness of the anti-adhesive layer calculated from the amount of application, etc.

[0169] 1mm in plan view of the anti-adhesive layer 2 The total number of particles in the square can be calculated by converting the total number of particles in this specified area (for example, 258×260 μm) to 1×1 mm.

[0170] In addition, the particle ratio and the area of ​​1 mm 2 As a microscope for determining the total number of particles within the square, for example, an OLS4000 laser microscope manufactured by Olympus Corporation can be used.

[0171] By providing an anti-adhesive layer in which the proportion of particles protruding from the anti-adhesive layer and the total number of particles in a specified area are within the above-mentioned ranges, scratches on the anti-adhesive layer and the light guide plate (diffusion plate) can be effectively prevented.

[0172] The same applies even when the sticking-prevention layer is laminated on the surface of the wavelength conversion sheet opposite to the light guide plate (diffusion plate) side and the sticking-prevention layer is in contact with the optical film. That is, by providing the sticking-prevention layer in which the ratio of particles protruding from the sticking-prevention layer and the total number of particles in a given area are within the above ranges, it is possible to effectively prevent the sticking-prevention layer and the optical film from being scratched.

[0173] In particular, when the optical film is a prism sheet, the prisms may chip depending on the shape of the prism sheet, making the optical film more susceptible to scratches than other optical films.

[0174] Therefore, when a prism sheet is used as the optical film, by laminating an anti-adhesive layer on the surface of the wavelength conversion sheet opposite the light guide plate (diffusion plate) side, in which the proportion of particles protruding from the anti-adhesive layer and the total number of particles in a specified area are within the above-mentioned ranges, it is possible to effectively prevent scratches on the optical film (prism sheet).

[0175] The particle 162 has a compressive strength of 2.8 kgf / mm 2 It is preferable that the resin contains a resin having a compressive strength of 3.0 kgf / mm or more. 2 More preferably, it is 4.0 kgf / mm 2 More preferably, it is 2.8kgf / mm or more. 2 The resin may be, for example, an acrylic resin. The compressive strength of the particles 162 is 2.8 kgf / mm 2 By satisfying the above, problems such as crushing or scraping of the particles by foreign matter are unlikely to occur, and foreign matter is unlikely to directly scratch the surface of the adhesion prevention layer, resulting in an effect of improving scratch resistance. The acrylic resin is a polymer containing, as a monomer component, at least one ethylenically unsaturated monomer having a carboxyl group or a carboxylate group selected from the group consisting of methacrylic acid, acrylic acid, methacrylic acid esters, and acrylic acid esters. Suppose the compressive strength of the particle 162 is 2.8 kgf / mm 2 If the thickness is less than this, when foreign matter or the like is mixed in, the particles are crushed or scraped, and the foreign matter is likely to directly scratch the surface of the sticking-preventive layer, thereby lowering scratch resistance, which is undesirable.

[0176] The thickness of the anti-adhesive layer is not particularly limited as long as it can achieve the effects of the present invention. For example, it is preferably 1.0 μm or more and 50.0 μm or less, and more preferably 1.5 μm or more and 10.0 μm or less. The thickness of the anti-adhesive layer means the thickness of the resin part other than the particles in the anti-adhesive layer, and does not include the thickness of the part of the particles that are exposed (exposed) above the resin. The thickness of the anti-adhesive layer can be measured, for example, by observing the cross section with a scanning electron microscope or the like.

[0177] In order to set the thickness of the anti-adhesive layer in the above range, the coating amount of the anti-adhesive layer after drying is 1.0 g / m 2 More than 3.6g / m 2 Within this range, it is possible to prevent particles from being embedded in the sticking-preventive layer and to prevent impurities from entering between the sticking-preventive layer and the light guide plate. If the coating amount of the sticking-preventive layer after drying is 1.0 g / m 2 If the thickness is less than 3.6 g / m, the anti-adhesive layer against particles will be too thin, and impurities may get between the anti-adhesive layer and the light guide plate (diffusion plate), damaging the matte layer or the light guide plate (diffusion plate). 2 If it is more than this amount, the particles may become embedded in the adhesion preventing layer, possibly impairing the function of the adhesion preventing layer.

[0178] The haze value of the sticking-preventing layer is preferably 10% or more and 35% or less, and more preferably 10% or more and 25% or less. When the haze value of the sticking-preventing layer is 10% or more, the number of particles contained in the sticking-preventing layer is sufficient, the scratch resistance of the sticking-preventing layer can be improved, and further, sticking between the sticking-preventing layer and the light guide plate or the like can be effectively suppressed. When the haze value of the sticking-preventing layer is 35% or less, the scratch resistance of the sticking-preventing layer can be improved, and the function as a display device can be improved.

[0179] If the haze value of the stick-preventing layer is less than 10%, the number of particles contained in the stick-preventing layer is insufficient, so the scratch resistance of the stick-preventing layer is deteriorated, and furthermore, the sticking between the stick-preventing layer and the light guide plate may not be effectively suppressed. If the haze value of the stick-preventing layer is more than 35%, the scratch resistance of the stick-preventing layer is deteriorated, and furthermore, the function as a display device is deteriorated because the haze value is too high. The haze value can be measured using a haze meter in accordance with JIS K7136. The haze value of the matte layer (stick-preventing layer) can be calculated by measuring the haze value after forming the stick-preventing layer on a substrate such as a PET film, and calculating the difference from the haze value of the substrate PET film alone.

[0180] (resin) The resin 161 contained in the sticking prevention layer is not particularly limited as long as it is a resin that can achieve the purpose of the sticking prevention layer, and examples thereof include acrylic resins, epoxy resins, urethane resins, polyester resins, polyester acrylate resins, polyurethane acrylate resins, acrylic urethane resins, epoxy acrylate resins, etc. Among these, acrylic resins are preferable from the viewpoint of hardness.

[0181] When an acrylic resin is contained, the proportion of the acrylic resin per 100 parts by mass of the resin contained in the sticking-preventive layer is preferably 60 parts by mass or more, and more preferably 80 parts by mass or more.

[0182] (particle) The particles are formed in a spherical shape, and suppress the light guide plate from sticking to the wavelength conversion sheet. The type of particles is not particularly limited, and examples thereof include acrylic resins, polystyrene resins, and polyethylene resins. The particles have a compressive strength of 2.8 kgf / mm2 or more as measured in accordance with JIS A 9511. 2 It is preferable that the resin contains one of the above resins, and examples of the resin include an acrylic resin and a polystyrene resin. In addition to the acrylic resin and polystyrene resin, the particles may be silica fine particles, melamine, nylon, benzoguanamine fine particles, etc. The hardness of these materials is, in order from highest to lowest, silica fine particles, melamine, nylon, polystyrene resin, acrylic resin, and polyethylene resin.

[0183] The average particle size of the particles is preferably 1 μm or more and 50 μm or less, and more preferably 1.5 μm or more and 10 μm or less. When the average particle size of the particles is 1 μm or more, at least a part of the particles is exposed from the surface of the sticking-preventing layer, and the sticking between the sticking-preventing layer and the light guide plate 330 can be more effectively suppressed, and the scratch resistance of the sticking-preventing layer can be improved. When the average particle size of the particles is 50 μm or less, it is possible to suppress the deterioration of the function of the sticking-preventing layer caused by the particles being detached from the sticking-preventing layer, and the occurrence of scratches on the sticking-preventing layer caused by the detached particles.

[0184] The average particle size is obtained as the D50 value in particle size distribution measurement based on, for example, JIS Z8820 and Z8822. The average particle size can be measured, for example, by a dynamic light scattering method, a laser diffraction scattering method, or by observation with a SEM or TEM.

[0185] The content of the particles is preferably 5% by mass or more and 50% by mass or less, and more preferably 10% by mass or more and 40% by mass or less, based on the total amount of the sticking-preventive layer. By having a content of 5% by mass or more, it is possible to more effectively prevent the sticking-preventive layer from sticking to other members such as a light guide plate. By having a content of 50% by mass or less, it is possible to ensure a sufficient amount of resin for forming the sticking-preventive layer, and the film-forming properties of the sticking-preventive layer are improved.

[0186] Of the particles contained in the adhesion-preventing layer, the content of particles protruding from the adhesion-preventing layer is preferably 2% by mass or more and 25% by mass or less, and more preferably 5% by mass or more and 20% by mass or less, based on the total amount of the adhesion-preventing layer.

[0187] The difference in refractive index between the particles and the resin contained in the sticking-preventive layer is preferably 0.5 or less, more preferably 0.3 or less, and even more preferably 0.1 or less.

[0188] (Additives) The sticking-preventing layer according to this embodiment may further contain additives such as stabilizers, curing agents, crosslinking agents, lubricants, ultraviolet absorbing agents, and the like, as necessary.

[0189] <Light diffusing layer> When the matte layer is a light diffusion layer, it can diffuse the light incident on and emerging from the wavelength conversion sheet, thereby further increasing the light wavelength conversion efficiency. Note that the light diffusion layer may not contain particles as long as it can form an uneven shape on the surface.

[0190] When the light diffusion layer contains a resin and particles, the same resin and particles as those contained in the sticking prevention layer can be used, and therefore a description thereof will be omitted here.

[0191] [Support] In the laminate according to the present embodiment, as shown in Figures 8 and 9, a support 150 may be disposed between the barrier film and the matte layer 160. The support 150 is a layer mainly containing a resin, and the same resin as that described for the substrate 120 can be used as the resin.

[0192] 8 and 9, the thickness of the support 150 is preferably more than 25 μm and not more than 200 μm, more preferably from 38 μm to 175 μm, and even more preferably from 50 μm to 150 μm. When the thickness of the support 150 is more than 25 μm and not more than 200 μm, the flexibility of the wavelength conversion sheet is improved, and the handleability when combined with a backlight light source of a display device is improved.

[0193] In order to avoid blocking of light from a backlight light source, the support preferably has a high total light transmittance as measured in accordance with JIS K 7361. Specifically, the support preferably has a total light transmittance as measured in accordance with JIS K 7361 of 85% or more, more preferably 90% or more.

[0194] [Adhesive layer] 8 and 9, the laminate according to this embodiment may have an adhesive layer 140 disposed between the barrier film and a support 150. The adhesive layer refers to a pressure-sensitive adhesive layer or an adhesive layer. Examples of adhesives that can be used to form the adhesive layer 140 include polyvinyl acetate adhesives, homopolymers of ethyl, butyl, 2-ethylhexyl ester of acrylic acid, and the like, and polyacrylic acid ester adhesives made of copolymers of these with methyl methacrylate, acrylonitrile, styrene, and the like, cyanoacrylate adhesives, ethylene copolymer adhesives made of copolymers of ethylene with monomers such as vinyl acetate, ethyl acrylate, acrylic acid, methacrylic acid, and the like, cellulose adhesives, polyester adhesives, polyamide adhesives, polyimide adhesives, amino resin adhesives made of urea resin or melamine resin, and the like, phenol resin adhesives, epoxy adhesives, polyurethane adhesives, reactive (meth)acrylic adhesives, rubber adhesives made of chloroprene rubber, nitrile rubber, styrene-butadiene rubber, and the like, silicone adhesives, and inorganic adhesives made of alkali metal silicates, low-melting point glass, and the like.

[0195] The adhesive constituting the adhesive layer is not particularly limited as long as it has the desired adhesive strength, and examples thereof include acrylic, urethane, rubber, and silicone adhesives. Among these, acrylic adhesives are preferred because they are excellent in durability such as heat resistance and transparency, and are low-cost. Examples of acrylic adhesives include acrylic ester copolymers obtained by copolymerizing acrylic esters with other monomers. Examples of acrylic esters include ethyl acrylate, n-butyl acrylate, 2-ethylhexyl acrylate, isooctyl acrylate, isononyl acrylate, hydroxyethyl acrylate, propylene glycol acrylate, acrylamide, and glycidyl acrylate, and these may be used alone or in combination of two or more.

[0196] Examples of the other monomers include methyl acrylate, methyl methacrylate, styrene, acrylonitrile, vinyl acetate, acrylic acid, methacrylic acid, itaconic acid, hydroxylethyl acrylate, hydroxylethyl methacrylate, propylene glycol acrylate, acrylamide, methacrylamide, glycidyl acrylate, glycidyl methacrylate, dimethylaminoethyl methacrylate, tert-butylaminoethyl methacrylate, n-ethylhexyl methacrylate, and the like. These may be used alone or in combination of two or more kinds.

[0197] The composition system of the adhesive layer may be any of the composition forms such as aqueous type, solution type, emulsion type, dispersion type, etc., and the properties may be any of the forms such as film / sheet type, powder type, solid type, etc., and further, the adhesive mechanism may be any of the forms such as chemical reaction type, solvent volatilization type, heat melting type, heat pressure type, etc.

[0198] The adhesive layer can be applied by, for example, roll coating, gravure coating, knife coating, dip coating, spray coating, other coating methods, or printing methods, and the coating amount is 0.1 g / m 2 More than 10g / m 2The following (dry state) is desirable.

[0199] Instead of the adhesive layer made of the adhesive, a resin layer made of, for example, a thermosetting resin or a thermoplastic resin containing a crosslinking agent, etc. may be laminated. Furthermore, a bonding method using extrusion lamination may be used in which a thermoplastic resin such as EVA, ionomer, polyvinyl butyral (PVB), polyethylene resin, etc. is melted and the molten thermoplastic resin is extruded and laminated.

[0200] <<Wavelength conversion sheet>> 10 and 11 are cross-sectional views showing an example of the wavelength conversion sheet of the present invention. Specifically, the wavelength conversion sheet 200B in FIG. 10 is formed by laminating a phosphor layer 110 containing phosphor 112 and sealing resin 111, and a laminate 100B on both surfaces of the phosphor layer 110 via a pressure-sensitive adhesive layer or adhesive layer 170 (hereinafter referred to as a tacky adhesive layer 170). The wavelength conversion sheet 200D in FIG. 11 is formed by laminating a phosphor layer 110 containing phosphor 112 and sealing resin 111, and a laminate 100D on both surfaces of the phosphor layer 110 via a tacky adhesive layer 170. By laminating the laminate of the present invention on both surfaces of the phosphor layer 110, the phosphor layer is given a barrier property. In this specification, both surface sides of the phosphor layer mean both the side on which the light source is located (light entrance side) and the side opposite to the side on which the backlight light source is located (light exit side) when the wavelength conversion sheet is used as a backlight light source.

[0201] 10 and 11, the matte layer is disposed on both outermost layers of the laminate, but the present invention may be configured such that the laminate is laminated only on the surface on the light guide plate or diffusion plate side (not shown). Also, the laminate may be laminated only on the surface on the light output side (viewing side) (not shown). Also, the matte layer may not be formed, and a barrier film as shown in FIG. 1 may be laminated alone on at least one surface of the phosphor layer.

[0202] [Phosphor layer] The phosphor layer 110 is a layer for adjusting the emission wavelength of the light emitted from the backlight light source. The phosphor layer 110 contains one or more types of phosphors made of quantum dots.

[0203] The quantum dots forming the phosphor 112 are semiconductor particles of a certain size having a quantum confinement effect. When the quantum dots absorb light from an excitation source and reach an energy excited state, they emit energy corresponding to the energy band gap of the quantum dots. By adjusting the size of the quantum dots or the material composition, the energy band gap can be adjusted, and energy in various levels of wavelength bands can be obtained. In particular, the quantum dots can generate strong fluorescence in a narrow wavelength band. This allows the display device to be illuminated with light of the three primary colors with excellent color purity, thereby providing a display device with excellent color reproducibility.

[0204] The phosphor is not particularly limited, and may be particles containing at least one selected from the group consisting of II-VI group compounds, III-V group compounds, IV-VI group compounds, and IV group compounds. From the viewpoint of luminous efficiency, the phosphor preferably contains a compound containing at least one of Cd and In.

[0205] Specific examples of II-VI compounds include CdSe, CdTe, CdS, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe, HgZnSTe, and the like. Specific examples of III-V compounds include GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs, InAlPSb, etc. Specific examples of IV-VI compounds include SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, SnPbSTe, and the like. Specific examples of Group IV compounds include Si, Ge, SiC, and SiGe.

[0206] The phosphor preferably has a core-shell structure. By making the band gap of the compound constituting the shell wider than that of the compound constituting the core, it is possible to further improve the quantum efficiency of the phosphor. Examples of combinations of the core and shell (core / shell) include CdSe / ZnS, InP / ZnS, PbSe / PbS, CdSe / CdS, CdTe / CdS, and CdTe / ZnS.

[0207] The phosphor may have a multi-layer shell structure, i.e., a core-multi-shell structure, in which one or more shells having a narrow band gap are laminated on a core having a wide band gap, and a shell having a wide band gap is further laminated on the shell, thereby making it possible to further improve the quantum efficiency of the phosphor.

[0208] The phosphor layer 110 can be formed by laminating sealing resin 111 containing phosphor 112. For example, it can be formed by applying a mixed liquid containing phosphor 112 and sealing resin 111 to the surface of the base layer and curing it. Examples of the sealing resin 111 include photopolymerization resins such as acrylic resins such as polyester (meth)acrylate, urethane (meth)acrylate, polyester-urethane (meth)acrylate, polyether (meth)acrylate, polyol (meth)acrylate, melamine (meth)acrylate, isocyanurate (meth)acrylate, epoxy (meth)acrylate, and (meth)acrylate resins, thermosetting resins such as phenol resin, urea resin, melamine resin, epoxy resin, unsaturated polyester resin, polyester resin, silicone resin, and polyurethane resin, and thermoplastic resins such as EVA, ionomer, polyvinyl butyral (PVB), and polyethylene-based resins containing a crosslinking agent or the like. From the viewpoint of adhesion between the phosphor layer and the base layer, it is preferable to include at least one resin selected from the group consisting of acrylic resin, epoxy resin, urethane resin, and polyester resin. These may be used alone or in combination. An adhesive layer may be formed to enhance adhesion.

[0209] [Adhesive layer] 3, the wavelength conversion sheet according to the present embodiment may have an adhesive layer 170 disposed between the laminate and the phosphor layer 110. As the adhesive layer 170, an adhesive similar to that described for the adhesive layer 140 can be used, and therefore a description thereof will be omitted here.

[0210] <Method of manufacturing wavelength conversion sheet> For example, the wavelength conversion sheet is produced by forming an adhesive layer 170 on the surface of the covering layer 130a side of two laminates 100B, and applying a mixed liquid (ink) containing phosphor 110 and sealing resin 111 to the surface of the adhesive layer of one of the laminates 100B. The mixed liquid (ink) is then brought into contact with the surface of the adhesive layer 170 of the other laminate 100B and cured, thereby producing the wavelength conversion sheet 200B shown in FIG. 10. The wavelength conversion sheet 200D shown in FIG. 11 can be produced in the same manner. It is also possible to apply the mixed liquid (ink) containing phosphor 110 and sealing resin 111 directly to the surface of the laminate without forming the adhesive layer 170.

[0211] <<Display device>> A display device including the above-mentioned wavelength conversion sheet will be described with reference to FIGS. FIG. 12 is a perspective view that illustrates a schematic configuration of a surface-mounted display device according to an embodiment of the present invention. Fig. 13 is a cross-sectional view of the display device shown in Fig. 12. The cross-sectional view shown in Fig. 13 is a cross-sectional view in a cross section parallel to the direction in which the wavelength conversion sheets 200B (200D) and the like constituting the display device are stacked, and parallel to the direction in which the light source unit and the light guide plate are arranged (the traveling direction of light emitted from the light source unit). FIG. 14 is a cross-sectional view that illustrates a schematic configuration of a direct-type display device according to one embodiment of the present invention.

[0212] 12 and 13, an LCD panel 360, a polarized light selective reflection sheet 350, a prism sheet 340, a wavelength conversion sheet 200B (200D), a light guide plate 330, and a reflection sheet 320 are laminated in this order. In addition, a light source section 310 is disposed in the display device 300A so as to be aligned along at least one end face (side face) of the light guide plate 330. The light source section 310, the light guide plate 330 or a diffusion plate 370 described later, and the wavelength conversion sheet 200B (200D) constitute a backlight member of the present invention. The LCD panel 360 is a transmissive display unit formed of a transmissive liquid crystal display element, and forms video information on its display surface. The polarized light selective reflection sheet 350 is a sheet-like member having a function of transmitting light in a specific polarization state and reflecting light in other polarization states, and for example, the DBEF series (manufactured by Sumitomo 3M Limited) can be used. When using such a polarized light selective reflection sheet 350, it is preferable to arrange the polarized light selective reflection sheet 350 so that the transmission axis of the sheet is parallel to the transmission axis of a polarizing plate (not shown) located on the light entrance side of the LCD panel 360, from the viewpoint of improving brightness and light utilization efficiency. Prism sheet 340 is an optical sheet that has the effect of deflecting (concentrating) the traveling direction of light emitted from the upper surface of light guide plate 330 toward the front (the normal direction of the panel surface of the LCD panel).

[0213] Light guide plate 330 is a substantially flat member that guides light. Light emitted by light source unit 310 is incident on light guide plate 330 from one end surface of the flat plate, and guides the light while being totally reflected by the upper and lower surfaces of light guide plate 330 within the light guide plate, and appropriately emits the light from the upper surface of light guide plate 330 to the prism sheet 340 side. The reflection sheet 320 is a sheet-like member capable of reflecting light, and is disposed on the opposite side of the light guide plate 330 from the prism sheet 340. The reflection sheet 320 has a function of reflecting the light emitted from the lower surface of the light guide plate 330 back into the light guide plate 330, thereby improving the efficiency of use of the light emitted from the light source unit 310. From the viewpoint of improving the efficiency of use of light, it is preferable that the reflection sheet 320 mainly has specular reflectivity (regular reflectivity). For example, the reflection sheet 320 may be a sheet-like member in which at least the reflection surface (the surface on the light guide plate 330 side) is formed of a material having a high reflectivity such as metal, or a sheet-like member including a thin film (e.g., a metal thin film) formed of a material having a high reflectivity as a surface layer. However, the reflection sheet 320 is not limited to this, and may be, for example, a sheet-like member made of a white resin having a high reflectivity and mainly having a diffuse reflectivity. The light source unit 310 is a light source that emits light to illuminate the LCD panel 360. The light source unit 310 is formed, for example, by arranging a plurality of point light sources at predetermined intervals from the viewpoint of uniformly inputting light to one end surface of the light guide plate 330. For example, an LED (Light Emitting Diode) light source or an organic EL (Electro Luminescence) light source is used as the point light source. 12 and 13 is a so-called surface mount type display device in which light irradiated from a light source unit 310, which is a backlight light source arranged on an end face of a light guide plate 330, enters the light guide plate 330, is guided within the light guide plate, and the light emitted from the upper face of the light guide plate 330 is transmitted in this order through a wavelength conversion sheet 200B (200D), a prism sheet 340, a polarization selective reflection sheet 350, and an LCD panel 360. The reflection sheet 320 is provided as necessary.

[0214] In the so-called surface mount display device 300A, the wavelength conversion sheet 200B (200D) is disposed so as to be in contact with the light guide plate 330. In the case of a conventional barrier film for a wavelength conversion sheet or a wavelength conversion sheet, the barrier film and the light guide plate are stuck together, which is a factor in significantly deteriorating the display characteristics of the liquid crystal display device. In addition, when the display device is transported, the wavelength conversion sheet and the light guide plate are rubbed against each other, which damages the wavelength conversion sheet and / or the light guide plate, which is a factor in deteriorating the display characteristics of the display device.

[0215] However, if a display device has a light guide plate disposed on the surface of the matte layer of the wavelength conversion sheet, even if the display device is a surface mount type display device, it is possible to effectively prevent the barrier film and the light guide plate from sticking to each other and to prevent the wavelength conversion sheet and / or the light guide plate from being damaged.

[0216] In addition, the light guide plate may be a conventionally known light guide plate, but in order to more effectively prevent the barrier film from sticking to the light guide plate, the surface of the light guide plate that comes into contact with the barrier film may be formed into a wedge shape.

[0217] Another display device including the above-mentioned wavelength conversion sheet will be described with reference to Fig. 14. The display device 300B in Fig. 14 is a so-called direct type display device in which a light source section 380 is arranged on the rear side of a diffusion plate 370, and a wavelength conversion sheet 200B (200D) is arranged on the opposite side of the diffusion plate 370 from the light source section 380, and the light irradiated from the light source section 380 is irradiated onto the wavelength conversion sheet 200B (200D) via the diffusion plate 370.

[0218] In this embodiment, a prism sheet 340, a polarized selective reflection sheet 350, and an LCD panel 360 are laminated in this order on the side opposite to the diffusion plate 370 of the wavelength conversion sheet 200B (200D) as in the display device 300A shown in Figs. 9 and 10 described above. A reflection sheet 320 is provided on the side opposite to the diffusion plate 370 of the light source unit 380, and light emitted from the light source unit 380 and reflected without entering the diffusion plate 370 is reflected back to the diffusion plate 370 side, thereby improving the light utilization efficiency. The light source unit 380 shown in Fig. 11 is formed by arranging a plurality of point light sources (LEDs) at equal intervals in a lattice pattern along the plate surface of the diffusion plate 370.

[0219] In the so-called direct-type display device 300B, the wavelength conversion sheet 200B (200D) is disposed so as to be in contact with the diffusion plate 370. By disposing the diffusion plate 370 on the surface of the matte layer 160 of the wavelength conversion sheet 200B (200D), it is possible to effectively prevent the barrier film and the diffusion plate from sticking to each other for the same reason as in the case of the display device 300A, and also to prevent the wavelength conversion sheet and / or the diffusion plate from being damaged.

[0220] <Display Device Manufacturing Method> The display device can be manufactured by a process of arranging a light guide plate or a diffusion plate on the surface of the matte layer of the wavelength conversion sheet.

[0221] <Suppression of black lines> When a wavelength conversion sheet is irradiated with primary light in an inspection process before being incorporated into a display device such as a liquid crystal display, a dark area such as a black line may occur in a part of the surface of the wavelength conversion sheet. The dark area tends to occur in a part of the surface of the wavelength conversion sheet. For this reason, by adopting only wavelength conversion sheets that do not include a dark area as a good product, a wavelength conversion sheet with no quality problems can be obtained. However, the above-mentioned selection method significantly reduces the yield of wavelength conversion sheets. For this reason, it is required to suppress the occurrence of dark areas such as black lines over time.

[0222] When the wavelength conversion sheet is illuminated with a commercially available blue LED or black light, the dark area such as a black line has a width of about 1 mm and a length of 50 mm or more, and can be visually confirmed. The present inventors have found that the dark area such as a black line is due to partial cracks in the barrier layer of the wavelength conversion sheet, which causes the quantum dots to deteriorate over time. The wavelength conversion sheet of the present invention can suppress the dark area such as a black line from occurring over time. Details will be described in the following examples. EXAMPLES

[0223] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these descriptions. First, barrier films according to Examples 1 to 4 and Comparative Examples 1 to 12 were produced using the film-forming apparatus 10 and film-forming method described in the present embodiment. Pretreatment conditions, deposition conditions, etc. are summarized in Tables 1 and 2.

[0224] Example 1 A biaxially oriented polyethylene terephthalate film (PET film, product name: PET-F manufactured by Unitika Ltd.) having a thickness of 12 μm was used as the substrate 1, and a plasma pretreatment step and a film formation step were carried out using the film formation apparatus 10 shown in FIG.

[0225] First, the PET substrate 1 used was a substrate that had been subjected to a humidity conditioning process in which the substrate was wound in a roll in an atmosphere of 25° C. and 50% RH, and then stored at 25° C. and 50% RH for 3 days to condition the humidity.

[0226] In the pretreatment step, the surface of the substrate 1 was subjected to plasma pretreatment using the plasma pretreatment mechanism 11B shown in Figures 2 and 3. Specifically, first, a plasma-forming gas was supplied to the plasma pretreatment chamber 12B using a plasma raw material gas supply unit, while the air pressure in the plasma pretreatment chamber 12B was adjusted using the reduced pressure chamber 12. Next, a voltage was applied between the pretreatment roller 20 and the electrode unit 21 to generate plasma, and the surface of the substrate 1 was subjected to plasma pretreatment. The plasma pretreatment was performed under the following conditions. <Pretreatment conditions> Substrate conveying speed: 670m / min High frequency power output: 4kW High frequency power supply frequency: 40kHz Plasma intensity: 550W·sec / m 2 Plasma forming gas: oxygen 100 (sccm), argon 1000 (sccm) Magnetic forming means: 1000 gauss permanent magnet Voltage applied between pretreatment drum and plasma supply nozzle: 420V Pressure in pretreatment compartment: 2.0×10 -1 Pa

[0227] In the film formation process, a vapor deposition film containing aluminum oxide was formed by a vacuum deposition method using a resistance heating type (RH in Table 1) evaporation mechanism 24 as shown in Fig. 6. Specifically, while aluminum metal wires were supplied into a boat 24b as a vapor deposition material, the vapor deposition material in the boat 24b was heated using the resistance heating type evaporation mechanism 24, and the aluminum was evaporated so as to reach the surface of the base material 1, and a vapor deposition film was formed on the surface of the base material 1 while supplying oxygen.

[0228] 6 and anodes (not shown) arranged on both sides in the width direction of the substrate 1 as viewed from the boat 24b and facing the opening of the hollow part of the hollow cathode 51 were used as the plasma supply mechanism 50, and plasma raw material gas (argon gas) was supplied to the hollow part of the hollow cathode 51, discharged to excite plasma, and the plasma was extracted by the opposing anode between the surface of the substrate 1 and the evaporation mechanism 24 to perform plasma assist during deposition. The conditions for plasma assist were an amount of argon gas supplied to the hollow cathode of 80 sccm, an anode current of 168 A, and an anode voltage of 23 V. Note that no plasma post-treatment process was performed after the plasma assist process during deposition.

[0229] The first vapor-deposited film was laminated on the substrate 1 by the above method. The conveying speed was 670 m / min, and the thickness of the vapor-deposited film was 8.0 nm. The light transmittance at a wavelength of 366 nm measured in-line after vapor deposition was set to 100% based on the transmittance of the substrate 1 before vapor deposition. After that, vapor deposition was started, and the oxygen supply rate was feedback-controlled so that the light transmittance was 99.7%. The pressure during vapor deposition was 1.1 Pa.

[0230] The barrier film roll that had been subjected to the above-mentioned film-forming process was subjected to an aging treatment at 55° C. and 50% RH for 3 days.

[0231] Furthermore, a first coating layer was laminated on the first vapor deposition film. As a water-soluble polymer, polyvinyl alcohol with a saponification degree of 99% or more and a degree of polymerization of 2400 was mixed with a liquid of water and isopropyl alcohol in a ratio of 95 / 5 to obtain solution A adjusted to a solid content of 4%. Water, isopropyl alcohol, and 1N hydrochloric acid were mixed in a ratio of 65 / 34 / 1 to obtain an adjusted solution B. As a metal alkoxide, tetraethoxysilane was prepared as solution C. A liquid obtained by adjusting the ratio of solution B and solution C and mixing the liquid obtained by adjusting the ratio of solution A and solution D was used as a barrier coating agent. The ratio of solution B to solution C and the ratio of solution A to solution D were adjusted so that the solid content of the barrier coating agent after mixing was 5%, and the mass of tetraethoxysilane converted to SiO2 was 2.0 relative to the solid content of PVA. This barrier coating agent was used as solution X.

[0232] The barrier coating agent prepared above was coated on the first vapor deposition film by the direct gravure method. It was then dried at 140°C to form a coating layer with a dry thickness of 200 nm, and then aged at 25°C and 50% RH for 3 days to form the first coating layer. The dry film thickness was controlled by changing the gravure plate.

[0233] Next, a second coating layer was formed on the first coating layer under the same conditions as for the first coating layer described above, and further, a second coating layer was formed on the second coating layer under the same conditions as for the first coating layer described above, except that the coating layer had a thickness of 230 nm, thereby producing the barrier film of Example 1.

[0234] Example 2 A barrier film of Example 2 was produced in the same manner as in Example 1, except that the plasma assist conditions were an anode current of 155 A and an anode voltage of 20 V.

[0235] Example 3 In the film formation process, the first and second vapor deposition films were formed under the same conditions as in Example 2, except that the conveying speed was 530 m / min, the oxygen supply amount was feedback controlled so as to achieve a light transmittance of 98.0%, the pressure during vapor deposition was 1.0 Pa, and the film thickness was 10.0 nm.

[0236] In the coating layer forming step, solution Y was used. When mixing solutions B and C, 5% of glycidoxypropyltrimethoxysilane was added relative to the weight of tetraethoxysilane, and then the ratio of solutions B and C and the ratio of solutions A and D were adjusted so that the solid content was 5% and the SiO2 equivalent mass of tetraethoxysilane was 3.4 relative to the solid content of PVA, to obtain a barrier coating agent that was solution Y. The barrier film of Example 3 was produced in the same manner as in Example 2, except that the first coating layer had a film thickness of 300 nm, the second coating layer had a film thickness of 300 nm, and the aging treatment after the coating layer formation was performed at 55°C and 50% RH for 3 days.

[0237] Example 4 In the film formation step, the conditions of the plasma assist were the same as in Example 3, except that the anode current was 141 A and the anode voltage was 22 V, to form the first and second vapor-deposited films.

[0238] In the coating layer forming step, the barrier film of Example 4 was produced in the same manner as in Example 2, except that solution X was used.

[0239] Comparative Example 1 In the film formation process of the first vapor-deposited film, the conveying speed was 600 m / min, the film thickness was 8.9 nm, and no aging treatment was performed after film formation, all of which were the same as in Example 2. In addition, no second vapor-deposited film was formed.

[0240] In the step of forming the first covering layer, solution Y was used in the same manner as in Example 3. The second covering layer was not formed, and the barrier film of Comparative Example 1 was produced.

[0241] Comparative Example 2 The barrier film of Comparative Example 2 was produced in the same manner as in Comparative Example 1, except that in the film-forming step of the first vapor-deposited film, the aging treatment after film formation was carried out at 50° C. and 50% RH for 2 days.

[0242] Comparative Example 3 A barrier film of Comparative Example 3 was produced in the same manner as in Comparative Example 1, except that in the film formation step of the first vapor-deposited film, the aging treatment after film formation was carried out at 55° C. and 50% RH for 3 days.

[0243] Comparative Example 4 In the film formation process of the first vapor deposition film, the oxygen supply amount was feedback-controlled so that the light transmittance was 94.0%, the pressure during vapor deposition was 0.3 Pa, the film thickness was 8.0 nm, and plasma assist was not performed, all of which were the same as in Comparative Example 3. No second vapor deposition film was formed.

[0244] In the step of forming the first coating layer, solution X was used in the same manner as in Example 1. The second coating layer was not formed, and the barrier film of Comparative Example 4 was produced.

[0245] Comparative Example 5 The same procedures as in Comparative Example 4 were carried out except that in the film formation process of the first vapor deposition film, an EB (electron beam) heating method (referred to as EB in Table 1) was used instead of a resistance heating method, the oxygen supply amount was feedback-controlled so that the light transmittance became 88.0%, and the pressure during vapor deposition was set to 0.2 Pa. A second vapor deposition film was not formed.

[0246] In the step of forming the first coating layer, solution X was used in the same manner as in Example 1. The second coating layer was not formed, and the barrier film of Comparative Example 5 was produced.

[0247] Comparative Example 6 A barrier film of Comparative Example 6 was produced in the same manner as in Example 1, except that in the film formation process, the plasma assist conditions were an anode current of 175 A and an anode voltage of 24 V.

[0248] Comparative Example 7 The barrier film of Comparative Example 7 was produced in the same manner as in Comparative Example 6, except that in the humidity conditioning step, the film was rolled up at 30°C and 60% RH and then stored at 30°C and 60% RH for 3 days to condition the humidity, and in the film formation step, the aging treatment after film formation was performed at 60°C and 50% RH for 4 days.

[0249] Comparative Example 8 A barrier film of Comparative Example 8 was produced in the same manner as in Example 2, except that in the film formation step, the aging treatment after film formation was not carried out.

[0250] Comparative Example 9 A barrier film of Comparative Example 9 was produced in the same manner as in Example 2, except that in the film formation process, the plasma assist conditions were an anode current of 47 A and an anode voltage of 21 V.

[0251] Comparative Example 10 The barrier film of Comparative Example 10 was produced in the same manner as in Example 2, except that in the film formation process, the conveying speed was 600 m / min, the oxygen supply amount was feedback-controlled so as to achieve a light transmittance of 94.0%, the pressure during deposition was 0.3 Pa, and plasma assist was not performed.

[0252] Comparative Example 11 In the film formation process, a biaxially oriented polyethylene terephthalate film (PET film, product name: P60 manufactured by Toray Industries, Inc.) having a thickness of 12 μm was used as the substrate 1, and an anchor coat layer (referred to as AC in Table 1) of an acrylic urethane resin was formed to a thickness of 200 nm on the substrate 1. The film formation process and aging treatment were performed in the same manner as in Example 3, except that an EB (electron beam) heating method (referred to as EB in Table 1) was used instead of a resistance heating method, a plasma pretreatment process was not performed, a conveying speed was 480 m / min, and the oxygen supply amount was feedback controlled so that the light transmittance of a wavelength of 366 nm measured in-line after deposition was 88.0%, the pressure during deposition was set to 0.2 Pa, and plasma assist was not performed. Note that the light transmittance of a wavelength of 366 nm measured in-line after deposition was set to a standard of 100% when there was a substrate 1 and an anchor coat layer and no deposition was performed.

[0253] In the coating layer forming step, solution Z was used. When mixing solutions B and C, 15% of 1,3,5-tris(3-trialkoxysilylpropyl)isocyanurate was added relative to the weight of tetraethoxysilane, and the ratio of solutions B and C and the ratio of solutions A and D were adjusted to mix the coating layer so that the solid content was 7% and the SiO2 equivalent mass of tetraethoxysilane was 4.0 relative to the solid content of PVA, to produce a barrier coating agent called solution Z, and the barrier film of Comparative Example 11 was produced in the same manner as in Example 3, except that the first coating layer had a thickness of 210 nm and the second coating layer had a thickness of 210 nm.

[0254] Comparative Example 12 A barrier film of Comparative Example 12 was produced in the same manner as in Comparative Example 11, except that in the coating layer forming step, the first coating layer had a thickness of 200 nm and the second coating layer had a thickness of 160 nm.

[0255] Comparative Example 13 In the film formation process of the first vapor deposition film in Example 2, an aging treatment after film formation was carried out at 60°C and 80% RH for 5 days, but the film broke when unwound to form the first coating layer, so no subsequent evaluation was performed.

[0256] [Table 1]

[0257] [Table 2]

[0258] [Acquisition and analysis of XAFS spectra] XAFS spectra were obtained under the following measurement conditions for the barrier films of Examples 1 to 4 and Comparative Examples 1 to 10. The results of Example 3 are shown in Figure 15. The vertical axis in the figure represents the intensity of the generated fluorescent X-rays (shown as absorption intensity (au) in the figure), and the horizontal axis represents the light (or X-ray) energy (eV).

[0259] <XAFS Spectrum Acquisition> · Utilized Beamline: BL1N2, Aichi Synchrotron Light Center · Accelerating Energy: 1.2 GeV · Beam Size: 1.0 mm (horizontal) × 1.0 mm (vertical) · Incident Angle to the Sample: 22.5° (assuming the vertical direction with respect to the sample is 0°) · Entrance Slit: 30 μm · Exit Slit: 30 μm · Measurement Method: Partial Fluorescence Yield Method · Energy Range (Al K-edge): 1500 - 1700 eV · Energy Step: 1500 - 1550 eV: 2.0 eV / step 1550 - 1555 eV: 1.0 eV / step 1555 - 1575 eV: 0.2 eV / step 1575 - 1600 eV: 0.5 eV / step 1600 - 1680 eV: 1.0 eV / step 1680 - 1700 eV: 2.0 eV / step (Integration Time: All 10 s / point) · Energy Calibration: Energy calibration using Au 4f 7 / 2 of the Au plate (calibrated with the value obtained by subtracting the theoretical value of 1500 eV from the measured value)

[0260] <XAFS Spectrum Analysis> Peak Separation Method The intensity values were normalized so that the absorption spectrum intensity value at the energy of the absorbed X-ray of 1540 eV was 0 and the absorption spectrum intensity value at the energy of the absorbed X-ray of 1680 eV was 1.

[0261]

Number

[0262] After standardization, data points from 1555eV to 1575eV and from 1595eV to 1605eV were extracted, and the above f(x) function was fitted to find each coefficient. However, the constraints k1=k2, K1=X1, K2=X2 were included. The fitting was performed using the least squares method. In this case, the least squares function in Python's scipy library was used, and the initial values ​​of the coefficients were given the values ​​in the table below. The symbols for the above functions are defined as follows: M i : Weighting factors of Gaussian and Lorentzian functions at the i-th absorption peak X i : Peak center of the i-th absorption peak h i : peak intensity factor for the i-th absorption peak β i : Peak width factor for the i-th absorption peak k j : the baseline intensity factor at the jth baseline K j : The half-point of the baseline intensity in the jth baseline

[0263] [Table 3]

[0264] The results of peak separation of the XAFS spectra of Example 3 and Comparative Examples 2, 4, and 11 are shown in Figures 16 to 19, respectively. Figure 16 shows the analysis result of separating the XAFS peaks of Example 3, Figure 17 shows the analysis result of separating the XAFS peaks of Comparative Example 2, Figure 18 shows the analysis result of separating the XAFS peaks of Comparative Example 4, and Figure 19 shows the analysis result of separating the XAFS peaks of Comparative Example 10.

[0265] Experiment is the measured XAFS spectrum. Fit.Peak1 is the intensity peak near 1566 eV that is separated, Fit.Peak2 is the intensity peak near 1568 eV that is separated, and Fit.Peak3 is the intensity peak near 1572 eV that is separated. From this, the result of calculating the XAFS peak top ratio P = (intensity peak top near 1572 eV) / (intensity peak top near 1566 eV) is shown in Table 4 for the barrier films of Examples 1 to 4 and Comparative Examples 1 to 10.

[0266] <TOF-SIMS Analysis> For the barrier films of Examples 1 to 4 and Comparative Examples 1 to 10, C2 - ions (mass number 24.000), CN - ions (mass number 26.0003), Si - ions (mass number 27.9777), AlO2 - ions (mass number 58.971), SiO2 - The intensities of ions (mass number 59.9666) were measured using time-of-flight secondary ion mass spectrometry (TOF-SIMS). Specifically, using a time-of-flight secondary ion mass spectrometer (manufactured by ION TOF, TOF.SIMS5), mass spectrometry of various ions in each layer was performed while repeatedly performing soft etching at a constant speed with a Cs (cesium) ion gun from the surface of the barrier film to the PET film side. The coating layer intensity ratio X = C2 - ion intensity / Si - ion intensity, and the results are shown in Table 4 (C2 / Si intensity ratio in Table 4). TOF-SIMS Measurement Conditions · Primary ion type: Bi 3++ (0.2 pA, 100 μs) · Measurement area: 150×150 μm 2 · Scan: 128 pixel×128 pixel×1 scan · Type of etching gun: Cs (1 keV, 60 nA) · Etching area: 600×600 μm 2 Etching rate: 10sec / cycle Vacuum time: 1×10 -6 >15 hours at <mbar The TOF-SIMS measurements were performed within 30 hours after the start of evacuation.

[0267] Graphical analyses of the measurement results are shown in Fig. 20 to Fig. 22. Fig. 20 shows the measurement results of Example 3, Fig. 21 shows the measurement results of Comparative Example 10, and Fig. 22 shows the measurement results of Comparative Example 11. In the figures, the unit of the vertical axis (intensity) is the intensity of secondary ions, and the unit of the horizontal axis (Et times (s)) is the number of seconds that etching was performed.

[0268] [Table 4]

[0269] <Measurement of the barrier properties of barrier films> For the barrier films of Examples 1 to 4 and Comparative Examples 1 to 10, the water vapor permeability and oxygen permeability were measured.

[0270] Water vapor permeability (g / (m 2 ·day), indicated as "WVTR" in the table) was measured using a water vapor transmission rate measuring device (manufactured by Mocon, product name "PERMATORAN-W 3 / 31") under the measurement conditions of 40°C and 100% RH in accordance with JIS K 7129 B method. In addition, oxygen transmission rate (cc / (m 2 The oxygen transmission rate (OTR) was measured using an oxygen transmission rate measuring device (manufactured by Mocon, product name "OX-TRAN 2 / 20") at 23°C and 90% RH in accordance with JIS K 7126-2. The results are shown in Table 5.

[0271] <Evaluation of Luminance Maintenance Rate> For the barrier films of Examples 1 to 4 and Comparative Examples 1 to 10, wavelength conversion sheets having the following layer configurations were prepared.

[0272] First, a matte layer 160 was formed on one surface of a support 150 (biaxially oriented PET film, thickness: 38 μm), and then an adhesive layer 140 (two-component curing polyurethane adhesive, thickness when dried: 5 μm) was applied thereon by a gravure roll coating method, dried, and laminated with the surface of the coating layer side of the barrier film 130 of Example 1 described above, to obtain two laminates 100D shown in FIG. 9.

[0273] The mat layer 160 is made of spherical particles containing a polyacrylic resin (Eposter MA (an acrylic crosslinked material having a compressive strength of 2.8 kgf / mm 2 The above resin (average particle size: 4 μm) was mixed with an acrylic resin to prepare a coating agent for forming a matte layer, which was then applied to the substrate by gravure roll coating (particle content: 1.7% by mass, dry coating amount: 1.6 g / m 2 , mat layer thickness 1.5 μm).

[0274] Next, the adhesive layer coating liquid described below was applied onto the surface of the base material 120 and dried to form an adhesive layer 170 . <Adhesive layer coating liquid> Polyester polyol 50 parts by weight (Hydroxyl value: 62 mg KOH / g, solid content: 20% by mass) Silane coupling agent 1 part by weight (3-Glycidoxypropylmethyldimethoxysilane) Silica filler 1 part by weight (Average particle size 5μm) Hardener 1 part by weight (1,6-hexamethylene diisocyanate, solid content 35% by mass) Solvent 50 parts by weight (Methyl ethyl ketone)

[0275] Furthermore, a phosphor coating solution containing the following phosphor 112 was applied onto the adhesive layer 170 surface formed on the base material 120 surface of one of the laminates 100D, and dried to form a phosphor layer 110 not irradiated with ionizing radiation. Next, the phosphor layer 110 not irradiated with ionizing radiation and the other laminate 100D were laminated so that their base materials 120 faced each other, and then ultraviolet rays were irradiated to laminate the two laminates 100D with the phosphor layer 110 having a thickness of 30 μm interposed therebetween, thereby producing the wavelength conversion sheet 200D shown in FIG.

[0276] <Phosphor dispersion liquid> In a glove box purged with nitrogen so that the oxygen concentration was 300 ppm or less, quantum dots and amino-modified silicone were mixed in the composition ratio shown below, and stirred for 4 hours with a magnetic stirrer while being heated in a water bath at 90° C. After that, the mixture was filtered through a polypropylene filter with a pore size of 0.2 μm to obtain a CdSe / ZnS core-shell quantum dot dispersion. Quantum dots 0.9 parts by weight (Emission peak: 540 nm, Sigma-Aldrich) Quantum dots 0.9 parts by weight (Emission peak: 630 nm, Sigma-Aldrich) Amino-modified silicone 99 parts by weight (Genesee, GP-344, viscosity: 670 mPa s) <Phosphor coating solution> Multifunctional acrylate compound 58.11 parts by weight (Ethoxylated bisphenol A diacrylate; Shin-Nakamura Chemical Co., Ltd.'s product name "ABE-300") Polyfunctional thiol compound 38.74 parts by mass (Pentaerythritol tetrakis(3-mercaptopropionate); trade name "PEMP" from SC Organic Chemicals) Photopolymerization initiator 0.5 parts by weight (IGM Resins BV's product name: "Omnirad TPO H") 1.61 parts by weight of the above phosphor dispersion liquid Acetic acid 0.79 parts by weight Titanium oxide 0.25 parts by weight (Chemours' product name "Typure R-706"; particle size 0.36 μm)

[0277] Similarly, wavelength-converting sheets were produced using the barrier films of Examples 2 to 4 and Comparative Examples 1 to 10 instead of the barrier film 130 of Example 1. After production, the wavelength-converting sheet was wound into a roll.

[0278] Each wavelength conversion sheet obtained above was cut into a size of 100 mm in width and 100 mm in length to obtain an evaluation sample. Then, the spectral radiance of the evaluation sample was measured using a spectroradiometer SR-LEDW (Topcon Corporation). The luminance of the peak tops near wavelengths of 449 nm, 535 nm, and 627 nm was determined as the luminance of blue, green, and red, respectively. The spectroradiometer was installed at the top, and a DBEF (Dual Brightness Enhancement Film), a BEF (Brightness Enhancement Film), an evaluation sample, a diffusion plate, and a blue LED light source were installed in this order under the objective lens of the spectroradiometer, and the spectral radiance was measured. The measurement angle was 0.1°.

[0279] The evaluation sample measured above was placed in a thermo-hygrostat at 60°C and 90% RH for 1000 hours to carry out a moist heat test, after which the luminance was measured in the same manner as above. The luminance maintenance rate of the evaluation sample was then calculated according to the following formula. The results are shown in Table 5. Luminance maintenance rate (535 nm) = (Ga / Ba) / (Gb / Bb) x 100 (%) Luminance maintenance rate (627 nm) = (Ra / Ba) / (Rb / Bb) x 100 (%) Ba: Emission intensity (brightness) of the peak top near 449 nm after moist heat test Ga: Emission intensity (brightness) of the peak top near 535 nm after moist heat test Ra: Emission intensity (brightness) of the peak top near 627 nm after moist heat test Bb: Emission intensity (brightness) of the peak top near 449 nm before the damp heat test Gb: Emission intensity (brightness) of the peak top near 535 nm before the damp heat test Rb: Emission intensity (brightness) of the peak top near 627 nm before the damp heat test

[0280] <Evaluation of the presence or absence of black lines> Each of the wavelength conversion sheets obtained above was cut into a size of 100 mm in width and 100 mm in length to obtain an evaluation sample. 100 samples were taken from the core side of the roll to the outside of the roll so that the sampling positions were not biased. A humidity test was performed by placing the samples in a thermo-hygrostat at 30°C and 90% RH for 1000 hours.

[0281] A backlight was prepared that was equipped with a direct-type blue LED with a central emission wavelength of 450 nm and a full width at half maximum of 20 nm as a light source. On the light emission side of the backlight light source, a light diffusion plate, a wavelength conversion sheet including a quantum dot-containing layer, a prism sheet, and a reflective polarizing plate (brightness enhancement film, manufactured by 3M, DBEF (registered trademark)) were arranged in this order. In addition, a reflective sheet was arranged on the side opposite to the light emission side of the light source.

[0282] The wavelength conversion sheet after the wet heat test was incorporated into the above-mentioned backlight, and the presence or absence of black lines was visually evaluated, n=100. The results are shown in Table 5.

[0283] [Table 5]

[0284] As shown in Tables 4 and 5, the laminate using the barrier film according to the present embodiment, in which the peak top ratio P obtained from the XAFS spectrum is 0.70 or more and less than 1.05, has a high luminance maintenance rate and does not produce black lines when used in a wavelength conversion sheet. [Explanation of symbols]

[0285] 100A Barrier Film 100B~100D laminate 110 Phosphor layer 111 Sealing resin 112 Phosphor 1, 120 base material 131b First deposition film 131a first coating layer 132b Second deposition film 132a Second coating layer 140 Adhesive layer or adhesive layer 150 Support 160 Matte Layer 161 Resin 162 particles 170 Adhesive layer or adhesive layer 200B, 200D Wavelength conversion sheet 300A, 300B display device 310, 380 light source section 320 Reflective Sheet 330 Light guide plate 340 Prism Sheet 350 Polarized selective reflective sheet 360 Liquid crystal panel (LCD panel) 370 Diffuser 10 Film deposition equipment P Plasma X Rotation Axis 11A Substrate transport mechanism 11B Plasma pretreatment mechanism 11C Film formation mechanism 12 Decompression Chamber 12A Substrate transport chamber 12B Plasma pretreatment chamber 12C Deposition chamber 13 Unwinding roller 14a~d Guide roll 15 Winding roller 20 Pre-treatment roller 21 Electrode part 23 Magnetic field forming part 23a 1st page 23b 2nd side 231 First Magnet 231c 1st axis direction part 232 Second Magnet 232c 2nd axis direction part 232d Connection part 24 Evaporation mechanism 24b Boat 25 Coating roller 31 Power supply wiring 32 Power supply 35a~35c Bulkhead 50 Plasma supply mechanism 51 Hollow Cathode 61 Vapor deposition material supply section 63 Aluminum Vapor

Claims

1. A barrier film comprising a resin substrate, a first aluminum oxide vapor-deposited film, a first coating layer, a second aluminum oxide vapor-deposited film, and a second coating layer laminated in this order, Each of the first coating layer and the second coating layer is a cured product of a resin composition containing an alkoxysilane and a hydroxyl group-containing water-soluble resin, a vapor-deposited film peak top ratio P of the first aluminum oxide vapor-deposited film and the second aluminum oxide vapor-deposited film, the vapor-deposited film peak top ratio P being equal to or greater than 0.70 and less than 1.05 when X-ray absorption fine structure analysis is performed from the second coating layer surface side of the barrier film, as defined below. P = (peak intensity top near 1572 eV) / (peak intensity top near 1566 eV)

2. 2. The barrier film according to claim 1, wherein when the barrier film is etched from a surface side opposite to the resin substrate by time-of-flight secondary ion mass spectrometry (TOF-SIMS), a coating layer intensity ratio X, defined as follows, detected in each region of the first coating layer and the second coating layer is 0.50 or more and 1.10 or less, respectively. X=C 2 - Ionic strength / Si - Ionic Strength

3. The barrier film according to claim 1 , further comprising a matte layer disposed on the resin substrate opposite to the first aluminum oxide vapor-deposited film.

4. A laminate comprising the barrier film according to claim 1 and a support laminated via an adhesive layer.

5. The laminate according to claim 4 , further comprising a matte layer disposed on the side of the support opposite to the adhesive layer.

6. A wavelength conversion sheet comprising the barrier films according to claim 3 disposed on both sides of a phosphor layer.

7. 5. A wavelength conversion sheet comprising the laminates according to claim 4 disposed on both sides of a phosphor layer, and each of the laminates is disposed in this order from the outermost layer side: the support, the resin base material, the covering layer, and the phosphor layer.

8. 5. A wavelength conversion sheet comprising the laminates according to claim 4 disposed on both sides of a phosphor layer, and each of the laminates is disposed in this order from the outermost layer side: the support, the covering layer, the resin base material, and the phosphor layer.

9. 5. A wavelength conversion sheet comprising the laminates according to claim 4 arranged on both sides of a phosphor layer, one laminate arranged in the order of the support, the resin base material, the covering layer, and the phosphor layer from the outermost layer side, and the other laminate arranged in the order of the support, the covering layer, the resin base material, and the phosphor layer from the outermost layer side.

10. A backlight member comprising: a light source; a light guide plate or a diffusion plate; and the wavelength conversion sheet according to claim 6.

11. A surface-mount display device including a light guide plate, A liquid crystal panel, a polarized light selective reflection sheet, a prism sheet, the wavelength conversion sheet according to claim 6, the light guide plate, and a reflection sheet are laminated in this order, A light source unit is disposed on an end surface of the light guide plate. Display device.

12. A direct-type display device equipped with a diffusion plate, A liquid crystal panel, a polarized light selective reflection sheet, a prism sheet, the wavelength conversion sheet according to claim 6, the diffusion plate, a light source unit, and a reflection sheet are laminated in this order. Display device.

Citation Information

Patent Citations

  • Aluminum oxide vapor deposition film and its production

    JP1999170427A

  • Laminate film and method for manufacturing the same

    JP2017177343A

  • Wavelength conversion sheet and backlight unit

    WO2015037733A1

Cited By

  • Fuel cell system

    EP4819257A1